Transfer sheet and method for producing the same, and molded article using the transfer sheet
By forming the transfer sheet A between the demolding base materials 1 and 2, and ensuring that the peel strength between the demolding base material 2 and the transfer layer is greater than the peel strength between the demolding base material 1 and the transfer layer, the problem that the transfer sheet functional layer in the prior art cannot fully perform its functions, and the full function of the adherend is achieved.
Patent Information
- Application Number
- CN202211367048.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-03-27
AI Technical Summary
In the prior art, when a transfer sheet is used to transfer the functional layer to the adherend, the problem of not being able to fully exert the function of the transferred functional layer frequently occurs.
By coating the transfer layer on the demolding base material 1 and stacking the demolding base material 2 on the transfer layer, a transfer sheet A with the demolding base material 1, the transfer layer and the demolding base material 2 is formed, so as to ensure that the peel strength between the demolding base material 2 and the transfer layer is greater than the peel strength between the demolding base material 1 and the transfer layer.
The full function imparting of the adherend is achieved, ensuring that the functional layer of the transfer layer can fully exert its functions, and improving the performance of the molded body.
Smart Images

Figure BDA0003922010710000191 
Figure BDA0003922010710000401 
Figure BDA0003922010710000431
Abstract
Description
[0001] This application is a divisional application. The application number of the original application is 202080031143.2, the application date is March 27, 2020, and the name of the invention is "Transfer sheet and its manufacturing method, and a molded body using the transfer sheet." Technical Field
[0002] The present invention relates to a transfer sheet and a method for producing the same, a method for producing a molded body using the transfer sheet and the molded body, and a front panel and an image display device using the molded body. Background Art
[0003] There are cases where it is required to impart predetermined functions such as antireflection and antifouling properties to the surface of any adherend. In such a case, for example, insert molding is performed.
[0004] Insert molding is a method of placing a functional film having a functional layer on a support in an injection molding mold, allowing injection resin to flow toward the support side, and integrating the support side of the functional film with the injection resin as an adherend to obtain a molded body.
[0005] However, in the case of insert molding, since a relatively thick support body is present between the adherend and the functional layer, there are problems such as an increase in the thickness of the entire molded body or a loss in the feel of the adherend.
[0006] On the other hand, the following means are also used: directly applying a functional coating on the surface of the adherend by spraying, etc., thereby giving a specified function to the surface of the adherend. The above-mentioned problem can be eliminated by this means. However, when directly applying to the surface of the adherend, there is a problem of uneven function due to uneven coating. In particular, when the surface of the adherend has a concave-convex shape, the problem of uneven coating tends to become significant.
[0007] Furthermore, as a means other than insert molding and direct coating, a means of forming a functional layer on an adherend by transfer using a transfer sheet has been proposed (Patent Documents 1 to 4).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-130298
[0011] Patent Document 2: Japanese Patent Application Publication No. 2009-072954
[0012] Patent Document 3: Japanese Patent Application Publication No. 2009-056674
[0013] Patent Document 4: Japanese Patent Application Publication No. 2008-151930 Summary of the invention
[0014] Problems to be solved by the invention
[0015] However, when the functional layer is transferred to an adherend using the transfer sheets disclosed in Patent Documents 1 to 4, the transferred functional layer frequently fails to fully function as compared to the case of insert molding or direct coating.
[0016] The object of the present invention is to provide a method for manufacturing a transfer sheet capable of imparting sufficient functions to an adherend and a transfer sheet. In addition, the object of the present invention is to provide a molded body imparted with sufficient functions by a transfer layer, a method for manufacturing the molded body, a front panel using the molded body, and an image display device.
[0017] Means for solving problems
[0018] The present invention to solve the above-mentioned problems provides the following solutions [1] to [6].
[0019] [1] A method for producing a transfer sheet, comprising:
[0020] In the method for producing the transfer sheet, the following steps (1) to (2) are performed in sequence:
[0021] Step (1), coating a transfer layer-forming coating liquid on a release substrate 1 to form a transfer layer including at least one functional layer; and
[0022] Step (2), stacking a release substrate 2 on the transfer layer to obtain a transfer sheet A which sequentially comprises the release substrate 1, the transfer layer and the release substrate 2, wherein the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer.
[0023] [2] The method for producing a transfer sheet according to [1] above, wherein:
[0024] In the method for producing the transfer sheet, the following step (3) is further performed:
[0025] Step (3): The release substrate 1 is peeled off from the transfer sheet A to obtain a transfer sheet B having the transfer layer on the release substrate 2.
[0026] [3] A method for producing a molded body, wherein:
[0027] In the method for producing the molded body, the following steps (4) to (5) are performed in sequence:
[0028] Step (4), obtaining a laminate C in which the surface of the transfer layer side of the transfer sheet B of the above-mentioned [2] is in close contact with an adherend; and
[0029] In step (5), the release substrate 2 is peeled off from the laminate C to obtain a molded body having a transfer layer on an adherend.
[0030] [4] A transfer sheet A, wherein the transfer sheet comprises a release substrate 1, a transfer layer and a release substrate 2 in sequence, the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer, the transfer layer comprises at least one functional layer, and at least one of the functional layers is functionally biased toward the release substrate 2 side.
[0031] [5] A transfer sheet B, wherein the transfer sheet has a transfer layer on a release substrate 2, the transfer layer includes at least one functional layer, and at least one of the functional layers has a function biased toward the release substrate 2 side.
[0032] [6] A molded body having a transfer layer on an adherend, the transfer layer having at least one functional layer, at least one of the functional layers having a function biased toward a side opposite to the adherend.
[0033] Effects of the Invention
[0034] According to the method for producing a transfer sheet of the present invention, a transfer sheet capable of imparting sufficient functions to an adherend can be easily produced. In addition, according to the transfer sheet of the present invention, a transfer sheet capable of imparting sufficient functions to an adherend can be easily produced.
[0035] In addition, according to the method for manufacturing a molded body of the present invention, a molded body having sufficient functions given by a transfer layer can be simply manufactured. In addition, according to the molded body of the present invention, a front panel using the molded body, and an image display device, the functions of the molded body having a transfer layer can be fully realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a cross-sectional view showing one embodiment of a semi-finished product of the release sheet A of the present invention.
[0037] Figure 2 This is a cross-sectional view showing one embodiment of the release sheet A of the present invention.
[0038] Figure 3 This is a cross-sectional view showing one embodiment of the release sheet B of the present invention.
[0039] Figure 4 It is a cross-sectional view showing one embodiment of each step of the method for producing a molded body of the present invention.
[0040] Figure 5 It is a cross-sectional view showing an example of a conventional transfer sheet and an example of a method for producing a molded body using the transfer sheet.
[0041] Figure 6 This is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed.
[0042] Figure 7 This is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed. DETAILED DESCRIPTION
[0043] [Method for producing transfer sheet]
[0044] In the method for producing a transfer sheet of the present invention, the following steps (1) to (2) are performed in order.
[0045] (1) coating a transfer layer-forming coating liquid on a release substrate 1 to form a transfer layer including at least one functional layer; and
[0046] (2) A release substrate 2 is stacked on the transfer layer to obtain a transfer sheet A which has the release substrate 1, the transfer layer and the release substrate 2 in sequence, and the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer.
[0047] Figure 1 This is a cross-sectional view showing one embodiment of a laminated body at a stage where step (1) is completed. Figure 1 The laminate has a transfer layer 30 on a release substrate 1 (10).
[0048] Figure 2 This is a cross-sectional view showing one embodiment of the transfer sheet A (100) obtained through the step (1) and the step (2). Figure 2 The transfer sheet A (100) has a transfer layer 30 and a release substrate 2 (20) on a release substrate 1 (10).
[0049] exist Figure 1 and Figure 2 In the embodiment, the transfer layer 30 includes two functional layers (functional layer 1 (31) and functional layer 2 (32)). Figure 1 and Figure 2 In the figure, the gradient of the functional layer 2 (32) indicates the degree of distribution of the functional components of the functional layer 2 (32) (the darker the color, the higher the density of the functional components).
[0050] <Step (1)>
[0051] Step 1 is a step of coating a transfer layer-forming coating liquid on a release substrate 1 to form a transfer layer including at least one functional layer.
[0052] The transfer layer-forming coating liquid may be applied to the release substrate 1 by gravure coating, die coating, bar coating, and other general coating methods. When the transfer layer has two or more functional layers, the functional layers may be formed sequentially or simultaneously by a coating device capable of simultaneously coating multiple layers.
[0053] Furthermore, after the transfer layer forming coating liquid is applied, it is preferably dried and / or irradiated with ultraviolet rays to volatilize the solvent or cure the resin composition as required.
[0054] <<Release substrate 1>>
[0055] The release substrate 1 can be used without particular limitation as long as it can be peeled from the transfer layer, but a plastic film is preferably used.
[0056] Examples of the plastic film used as the release substrate 1 include plastic films formed from one or more of polyolefin resins such as polyethylene and polypropylene, vinyl resins such as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, acrylic resins such as polymethyl (meth)acrylate and polyethyl (meth)acrylate, styrene resins such as polystyrene, polyamide resins such as nylon 6 and nylon 66, cellulose resins such as triacetyl cellulose, polycarbonate resins, and polyimide resins.
[0057] The release substrate 1 is preferably surface-released with a release agent such as a fluorine-based release agent or a silicone-based release agent from the viewpoint of improving the releasability from the transfer layer and making the peel strength 2 greater than the peel strength 1 .
[0058] In addition, from the above two viewpoints, the surface shape of the release substrate 1 is preferably substantially smooth. Specifically, the arithmetic mean roughness Ra of the surface of the release substrate 1 on the side where the transfer layer is formed is preferably 0.04 μm or less at a cutoff value of 0.25 mm in JIS B0601:1994. Regarding the Ra of the release substrate 1, for example, a sample for evaluation is prepared by laminating a black acrylic plate (manufactured by KURARAY, trade name "Comoglass 502K") to the surface of the release substrate 1 cut into 100 mm × 100 mm on the side where the transfer layer is not laminated, with a transparent adhesive (manufactured by Hitachi Chemical Co., Ltd., trade name "DA-1000") interposed therebetween, and the sample is placed on a horizontal surface, and can be measured under the following measurement conditions.
[0059] <Measurement conditions of Ra>
[0060] ·Reference length (cut-off value λc of roughness curve): 0.25 mm
[0061] ·Evaluation length (reference length (cut-off value λc) × 5): 1.25 mm
[0062] ·Feed speed of the stylus: 0.1 mm / s
[0063] ·Longitudinal magnification: 100,000 times
[0064] ·Transverse magnification: 50 times
[0065] ·Sliding: Not adopted (no contact with the measurement surface)
[0066] ·Type of cut-off filter: Gaussian filter
[0067] ·JIS mode: JIS1994
[0068] In addition, from the viewpoint of suppressing peeling static electricity, the release substrate 1 may also have an antistatic layer.
[0069] Although not particularly limited, from the viewpoint of operability, the thickness of the release substrate 1 is preferably 10 to 500 μm, more preferably 20 to 400 μm, and further preferably 30 to 300 μm. In addition, from the viewpoint of making the entire transfer sheet A softer and thus improving the operability, the upper limit value of the thickness of the release substrate 1 is more preferably 90 μm or less, and most preferably 45 μm or less.
[0070] In addition, when the thickness of the release substrate 1 is T1 and the thickness of the release substrate 2 is T2, from the viewpoint of operability after peeling off the release substrate 1, T2 / T1 is preferably more than 1.00, more preferably 1.10 or more, and further preferably 1.20 or more. In addition, from the viewpoint of suppressing the curling of the transfer sheet, T2 / T1 is preferably 2.00 or less, more preferably 1.80 or less, and further preferably 1.60 or less.
[0071] <<Transfer layer>>
[0072] The transfer layer is the layer transferred onto the adherend and has the function of imparting a specified function to the adherend.
[0073] The transfer layer includes at least one functional layer. The number of functional layers included in the transfer layer can be only 1 layer, or can be 2 layers as Figures 1-2 such, and further can be 3 layers or more.
[0074] Examples of the functional layer include a hard coat layer, a low refractive index layer, a high refractive index layer, an antiglare layer, an antifouling layer, a stress relaxation layer, an antistatic layer, a gas barrier layer, an ultraviolet absorption layer, a coloring layer, a specific wavelength absorption layer, an antifog layer, and a transparent conductive layer.
[0075] In addition, the functional layer can also be a layer formed by compounding two or more of the above functions. That is, in this specification, the description of each functional layer such as hard coating, low refractive index layer, high refractive index layer, anti-glare layer, antifouling layer, stress relaxation layer, antistatic layer, gas barrier layer, ultraviolet absorption layer, coloring layer, specific wavelength absorption layer, antifog layer and transparent conductive layer not only refers to the functional layer with a single function, but also refers to the functional layer with a composite function. For example, the hard coating includes antifouling hard coating, anti-glare hard coating and high refractive index hard coating, etc. In addition, the antifouling layer includes anti-glare antifouling layer and low refractive index antifouling layer, etc.
[0076] The transfer layer may have, in addition to the functional layer, other layers that do not impart a special function to the adherend, such as an adhesive layer and an anchor layer.
[0077] The adhesive layer has the function of being arranged between functional layers to improve interlayer adhesion of functional layers or being located on the farthest side of the release substrate 2 to improve adhesion between the transfer layer and the adherend. The adhesive layer can be formed from an adhesive layer-forming coating liquid containing a general-purpose resin component showing adhesion.
[0078] Furthermore, when the functional layer has adhesiveness and the adhesion between the functional layer and the adherend is good, or when a double-sided adhesive sheet is used for making the transfer layer and the adherend adhere closely, the adhesive layer may not be provided on the farthest side of the release substrate 2 .
[0079] The adhesive layer may be a pressure-sensitive adhesive layer (so-called pressure-sensitive adhesive layer) or may be an adhesive layer having heat sealability.
[0080] In addition, when the adhesive layer is arranged at the position farthest from the release substrate 2 (the position in contact with the release substrate 1), the adhesive layer is preferably a heat-sealable adhesive layer. Since the heat-sealable adhesive layer has almost no stickiness at room temperature, the transfer sheet B formed by peeling the release substrate 1 from the transfer sheet A can be rolled up into a roll, which can improve the workability. In addition, by making the adhesive layer have heat-sealability, the peel strength 2 can be easily made greater than the peel strength 1.
[0081] The thickness of the adhesive layer is preferably 0.5 to 50 μm, more preferably 1 to 30 μm, and even more preferably 2 to 20 μm.
[0082] The anchor layer has the following functions: for example, by forming the anchor layer closer to the release substrate 1 than the functional layer (farther from the release substrate 2 than the functional layer), the functional layer is protected from heat of the injection resin during in-mold molding described later.
[0083] The anchor layer preferably includes a cured product of a curable resin composition.
[0084] Examples of the curable resin composition include thermosetting resin compositions and ionizing radiation curable resin compositions. The resin composition may be a single type or a mixture of a plurality of types.
[0085] The embodiment of the ionizing radiation curable resin composition of the anchor layer is the same as the embodiment of the ionizing radiation curable resin composition of the hard coat layer described later.
[0086] The thermosetting resin composition of the anchor layer is a composition containing at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of the thermosetting resin include acrylic resins, polyurethane resins, phenolic resins, urea melamine resins, epoxy resins, unsaturated polyester resins, silicone resins, and the like. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.
[0087] The thickness of the anchor layer is preferably 0.1 to 6 μm, more preferably 0.5 to 5 μm.
[0088] Specific examples of the functional layer included in the transfer layer include the following (1) to (9). In addition, in the following (1) to (9), " / " represents the interface of each functional layer, and the right side represents the side of the release substrate 2. In addition, in the following (1) to (9), the antifouling layer, hard coating layer, high refractive index layer, low refractive index layer and antiglare layer can also be composite functional layers with other functions. For example, the antifouling layer of (1), the antiglare layer of (5), and the antiglare layer of (6) preferably have hard coating properties.
[0089] (1) Antifouling layer
[0090] (2) Hard coating / antifouling layer
[0091] (3) Hard coating / high refractive index layer / antifouling low refractive index layer
[0092] (4) High refractive index hard coating / antifouling low refractive index layer
[0093] (5) Anti-glare layer
[0094] (6) Anti-glare layer / low refractive index layer
[0095] (7) Hard coating / anti-glare layer
[0096] (8) Hard coating layer / anti-glare layer / anti-fouling low refractive index layer
[0097] (9) Anti-glare layer / hard coating layer / anti-fouling low refractive index layer
[0098] Hereinafter, the hard coat layer, the low refractive index layer, the high refractive index layer, the antiglare layer, and the antifouling layer, which are representative examples of the functional layer, will be specifically described.
[0099] ―Hard Coating―
[0100] From the viewpoint of wear resistance, the hard coating layer as an example of the functional layer preferably comprises a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, and more preferably comprises a cured product of an ionizing radiation curable resin composition. The resin composition may be one kind or a mixture of two or more kinds.
[0101] Thermosetting resin composition is a composition containing at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of thermosetting resins include acrylic resins, polyurethane resins, phenolic resins, urea melamine resins, epoxy resins, unsaturated polyester resins, silicone resins, and the like. In the thermosetting resin composition, a curing agent is added to these curable resins as required.
[0102] Ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). As the ionizing radiation curable functional group, ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, allyl, and epoxy, oxetanyl, etc. can be cited. As the ionizing radiation curable compound, it is preferably a compound having an ethylenically unsaturated bond group, more preferably a compound having more than two ethylenically unsaturated bond groups, wherein it is further preferably a (meth) acrylate compound having more than two ethylenically unsaturated bond groups. As the (meth) acrylate compound having more than two ethylenically unsaturated bond groups, any one of a monomer and an oligomer can be used.
[0103] In addition, ionizing radiation refers to rays with energy quanta in electromagnetic waves or charged particle beams that can cause molecules to polymerize or cross-link. Ultraviolet rays (UV) or electron beams (EB) are usually used, but in addition to these, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays may also be used.
[0104] In the present specification, (meth)acrylate refers to acrylate or methacrylate, (meth)acrylic acid refers to acrylic acid or methacrylic acid, and (meth)acryloyl refers to acryloyl or methacryloyl.
[0105] From the viewpoint of wear resistance, the thickness of the hard coating layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, from the viewpoint of easily suppressing cracks in the transfer layer during transfer, the thickness of the hard coating layer is preferably 100 μm or less, more preferably 50 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less.
[0106] ―Low refractive index layer―
[0107] The low refractive index layer as an example of the functional layer has the effect of improving the anti-reflective property of the adherend. In the case where the transfer layer has more than two functional layers, the low refractive index layer is preferably formed on the side farthest from the demoulding substrate 1. In addition, the low refractive index layer preferably has antifouling property. That is, the low refractive index layer is preferably an antifouling low refractive index layer.
[0108] Furthermore, by forming a high refractive index layer to be described later on the release substrate 1 side of the low refractive index layer so as to be adjacent to the low refractive index layer, the antireflection property can be further improved.
[0109] The refractive index of the low refractive index layer is preferably 1.10 to 1.48, more preferably 1.20 to 1.45, more preferably 1.26 to 1.40, more preferably 1.28 to 1.38, and more preferably 1.30 to 1.32. In this specification, the refractive index of the low refractive index layer and the high refractive index layer refers to the refractive index at a wavelength of 589.3 nm.
[0110] The thickness of the low refractive index layer is preferably 80 to 120 nm, more preferably 85 to 110 nm, and more preferably 90 to 105 nm. The thickness of the low refractive index layer is preferably larger than the average particle size of the low refractive index particles such as hollow particles.
[0111] The method of forming the low refractive index layer can be roughly divided into a wet method and a dry method. As the wet method, there can be mentioned a method of forming by a sol-gel method using a metal alkoxide or the like, a method of forming by coating a low refractive index resin such as a fluororesin, and a method of forming by coating a low refractive index layer forming coating liquid containing low refractive index particles in a resin composition. As the dry method, there can be mentioned a method of forming the low refractive index layer by a physical vapor deposition method or a chemical vapor deposition method, and as materials, there can be mentioned SiO2, SiO x (x=1~2), MgF2, etc.
[0112] The wet method is superior to the dry method in terms of production efficiency, suppression of oblique reflection hue and chemical resistance. In the present invention, for the wet method, from the viewpoint of adhesion, water resistance, wear resistance and low refractive index, it is preferably formed by a low refractive index layer forming coating liquid containing low refractive index particles in the binder resin composition. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used, but the curable resin composition described later is preferably used.
[0113] The low refractive index layer is usually located on the outermost surface of the molded body formed by transferring the transfer layer to the adherend. Therefore, the low refractive index layer requires good wear resistance. Regarding the wear resistance of the low refractive index layer, the smoother the surface shape, the better the tendency.
[0114] In the conventional transfer method, the surface shape of the low refractive index layer is generally smooth. The reason is believed to be that in the conventional transfer method, a resin coating having substantially no low refractive index particles exists near the interface of the low refractive index layer with the release substrate, and after transfer, the resin coating is located on the outermost surface of the molded body, and the surface of the resin coating reflects the surface shape of the release substrate and is smooth.
[0115] On the other hand, when the transfer sheet A of the present invention is used, the surface of the low refractive index layer on the outermost surface of the molded body is prone to tiny concave-convex caused by low refractive index particles. In addition, in recent years, in order to reduce the refractive index of the low refractive index layer, hollow particles with large particle size are used as low refractive index particles. The inventors have found the following subject: Even when the surface of such a low refractive index layer is wiped with an object only attached with fine solids (such as gravel) or an object only attached with oil, damage cannot be seen, when wiping with an object attached with both solids and oil, damage will occur (hereinafter, this subject is sometimes referred to as "oil dust resistance"). The action of wiping with an object attached with solids and oil is, for example, equivalent to the action of a user operating a touch panel type image display device with a finger attached with oil contained in cosmetics and food, etc. and gravel contained in the atmosphere.
[0116] The inventors have studied, and the results show that the above damage is mainly caused by the partial loss of the hollow particles contained in the low refractive index layer or the falling off of the hollow particles. As the reason, such a reason is considered: the concave-convex caused by the hollow particles formed on the surface of the low refractive index layer is larger. That is, if the surface of the low refractive index layer is wiped with a finger attached with solids and oil, the finger moves on the surface of the low refractive index layer under the state that the oil becomes a binder and the solids are attached to the finger. At this time, it can be imagined that the phenomenon that a part of the solids (such as the sharp part of the gravel) easily enters the concave portion of the surface of the low refractive index layer and the solids entering the concave portion pass through the concave portion and cross the convex portion (hollow particles) together with the finger, and at this time, a larger force can be applied to the convex portion (hollow particles), so the hollow particles can be damaged or fall off. In addition, it can be imagined that the resin itself located in the concave portion is also damaged by the wiping of the solids, so that the hollow particles are more likely to fall off due to the damage of the resin.
[0117] The present inventors have conducted intensive studies and have found that, in order to impart oil dust resistance, it is effective to use hollow particles and non-hollow particles as low-refractive index particles and to uniformly disperse the hollow particles and the non-hollow particles. Figure 6 A cross-sectional photograph showing a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed, Figure 7 This is a cross-sectional photograph of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed. Figure 6 and Figure 7 The cross-sectional photograph was obtained by observation using an electron microscope H-7650 manufactured by Hitachi High-Technologies Corporation under the conditions of an emission current of 10 μA, an acceleration voltage of 100 keV, and a filament voltage of 20 V.
[0118] In order to lower the refractive index of the low refractive index layer and improve the oil dust resistance, the low refractive index particles preferably include hollow particles and non-hollow particles.
[0119] The material of the hollow particles and the non-hollow particles can be any inorganic compound or organic compound such as silica and magnesium fluoride, but silica is preferred from the viewpoint of low refractive index and strength. The following description will focus on hollow silica particles and non-hollow silica particles.
[0120] Hollow silica particles refer to particles that have an outer shell layer made of silica, and the inside of the particles surrounded by the outer shell layer is a cavity, and the cavity contains air. Hollow silica particles are particles whose refractive index is reduced in proportion to the gas occupancy rate compared with the original refractive index of silica by containing air. Non-hollow silica particles are particles that do not have a cavity inside like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.
[0121] The shapes of the hollow silica particles and non-hollow silica particles are not particularly limited, and may be substantially spherical shapes such as true spheres, rotational ellipsoids, and polyhedrons that can approximate spheres. Of these, true spheres, rotational ellipsoids, or substantially spherical shapes are preferred in consideration of wear resistance.
[0122] Because hollow silica particles contain air inside, the refractive index of the low refractive index layer as a whole is reduced. By using hollow silica particles with a large particle size that improves the ratio of air, the refractive index of the low refractive index layer can be further reduced. On the other hand, hollow silica particles have a tendency to deteriorate in mechanical strength. Especially in the case of hollow silica particles with a large particle size that improves the ratio of air, there is a tendency that easily causes the wear resistance of the low refractive index layer to decrease.
[0123] The non-hollow silica particles play a role in improving the abrasion resistance of the low refractive index layer by being dispersed in the binder resin.
[0124] In order to make the binder resin contain hollow silica particles and non-hollow silica particles at a high concentration and make the particles uniformly dispersed in the resin along the film thickness direction, it is preferred to set the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles in a manner that the hollow silica particles are close to each other and the non-hollow particles enter the hollow silica particles. Specifically, the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles (the average particle size of the non-hollow silica particles / the average particle size of the hollow silica particles) is preferably less than 0.29, more preferably less than 0.20. In addition, the ratio of the average particle size is preferably more than 0.05. If optical properties and mechanical strength are taken into account, the average particle size of the hollow silica particles is preferably more than 50nm and less than 100nm, more preferably more than 60nm and less than 80nm. Furthermore, in consideration of dispersibility while preventing aggregation of the non-hollow silica particles, the average particle size of the non-hollow silica particles is preferably 5 nm to 20 nm, and more preferably 10 nm to 15 nm.
[0125] The surfaces of the hollow silica particles and the non-hollow silica particles are preferably coated with a silane coupling agent, and more preferably a silane coupling agent having a (meth)acryloyl group or an epoxy group is used.
[0126] By subjecting the silica particles to a surface treatment using a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and aggregation of the silica particles is less likely to occur. Therefore, the silica particles are easily dispersed uniformly.
[0127] Examples of the silane coupling agent include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, -Triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane, etc. In particular, it is preferable to use one or more selected from 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane and 3-methacryloxypropyltriethoxysilane.
[0128] The more the content of the hollow silica particles, the higher the filling rate of the hollow silica particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, the content of the hollow silica particles is preferably 100 parts by mass or more, more preferably 150 parts by mass or more relative to 100 parts by mass of the binder resin.
[0129] On the other hand, if the content of hollow silica particles relative to the binder resin is too much, the hollow silica particles exposed from the binder resin increase, and the binder resin combined between the particles decreases. Therefore, there is a tendency that the hollow silica particles are easily damaged or fall off, so that the mechanical strength such as the wear resistance of the low refractive index layer is reduced. In addition, if the content of hollow silica particles is too much, there is a tendency that the transfer adaptability is impaired. Therefore, the content of hollow silica particles is preferably less than 400 mass parts relative to 100 mass parts of binder resin, and more preferably less than 300 mass parts.
[0130] If the content of non-hollow silica particles is less, even if there are non-hollow silica particles on the surface of the low refractive index layer, sometimes the hardness rise will not be affected. In addition, if a large number of non-hollow silica particles are contained, the impact of the shrinkage unevenness caused by the polymerization of the binder resin can be reduced, and the concavo-convex produced on the surface of the low refractive index layer after the resin is cured can be reduced. By reducing the concavo-convex on the surface of the low refractive index layer, it is possible to make the oil dust resistance and antifouling property good, which is preferred in this regard. Therefore, the content of non-hollow silica particles is preferably more than 90 mass parts relative to 100 mass parts of the binder resin, and more preferably more than 100 mass parts.
[0131] On the other hand, if the content of non-hollow silica particles is too much, non-hollow silica is easily condensed, resulting in uneven shrinkage of the binder resin, so that the surface concave-convex becomes larger. In addition, if the content of non-hollow silica particles is too much, there is a tendency that transfer adaptability is impaired. Therefore, the content of non-hollow silica particles is preferably less than 200 mass parts relative to 100 mass parts of binder resin, and more preferably less than 150 mass parts.
[0132] By including hollow silica particles and non-hollow silica particles in the binder resin at the above ratio, the barrier properties of the low refractive index layer can be improved. This is presumably because the silica particles are uniformly dispersed at a high filling rate, thereby inhibiting the permeation of gas or the like.
[0133] In addition, various cosmetics such as sunscreen and hand cream sometimes contain low-volatile low-molecular polymers. By making the barrier property of the low-refractive index layer good, it is possible to inhibit the low-molecular polymer from penetrating into the coating film of the low-refractive index layer, thereby inhibiting the adverse conditions (such as abnormal appearance) caused by the low-molecular polymer remaining in the coating film for a long time.
[0134] The binder resin of the low refractive index layer preferably comprises a cured product of an ionizing radiation curable resin composition. In addition, as the ionizing radiation curable compound contained in the ionizing radiation curable resin composition, a compound having an ethylenically unsaturated bond group is preferred. Among them, a (meth)acrylate compound having a (meth)acryloyl group is more preferred.
[0135] Hereinafter, a (meth)acrylate compound having 4 or more ethylenically unsaturated bond groups is referred to as a "multifunctional (meth)acrylate compound". In addition, a (meth)acrylate compound having 2 to 3 ethylenically unsaturated bond groups is referred to as a "low-functional (meth)acrylate compound".
[0136] As (meth) acrylate compounds, any one of monomers and oligomers can be used. In particular, from the viewpoint of suppressing uneven shrinkage during curing and making it easy to smooth the concavo-convex shape of the low refractive index layer surface, the ionizing radiation curable compound further preferably includes a low-functional (meth) acrylate compound. By smoothing the concavo-convex shape of the low refractive index layer surface, it is possible to make the oil dust resistance and antifouling property good, which is preferred at this point. It is also preferred to use a low-functional (meth) acrylate compound in terms of making the transfer adaptability of the transfer layer good.
[0137] The proportion of the low-functional (meth)acrylate compound in the ionizing radiation-curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass.
[0138] Furthermore, from the viewpoint of suppressing shrinkage unevenness during curing and making it easier to smooth the unevenness of the surface of the low refractive index layer, the low-functional (meth)acrylate compound is preferably a bifunctional (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0139] Examples of the bifunctional (meth)acrylate compounds among the (meth)acrylate compounds include isocyanuric acid di(meth)acrylate, polyalkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, and polytetramethylene glycol di(meth)acrylate, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, and 1,6-hexanediol diacrylate.
[0140] Examples of the trifunctional (meth)acrylate compound include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.
[0141] Examples of the tetrafunctional or higher polyfunctional (meth)acrylate-based compounds include pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol tetra(meth)acrylate.
[0142] These (meth)acrylate compounds may be modified as described below.
[0143] Examples of the (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.
[0144] Urethane (meth)acrylate is obtained by, for example, a reaction between a polyol and an organic diisocyanate and a hydroxy (meth)acrylate.
[0145] In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid, (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc., and polybasic acids with (meth)acrylic acid, and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc., and phenols with (meth)acrylic acid.
[0146] In addition, from the viewpoint of suppressing the uneven shrinkage caused by cross-linking and improving the smoothness of the surface, the above-mentioned (meth) acrylate compounds can also modify a part of the molecular skeleton. By smoothing the concavo-convex shape of the low refractive index layer surface, it is possible to make the oil dust resistance and antifouling property good, which is preferred in this regard. For example, (meth) acrylate compounds modified by ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. can be used. In particular, from the viewpoint of improving the affinity with low refractive index particles (silicon dioxide particles therein) and suppressing the agglomeration of low refractive index particles, the above-mentioned (meth) acrylate compounds are preferably modified with alkylene oxides such as ethylene oxide and propylene oxide. The ratio of the (meth) acrylate compounds modified by alkylene oxide in the ionizing radiation curing compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass. The alkylene oxide-modified (meth)acrylate compound is preferably a low-functional (meth)acrylate compound, and more preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0147] As the (meth)acrylate compound having two ethylenically unsaturated bond groups modified by alkylene oxide, bisphenol F alkylene oxide-modified di(meth)acrylate, bisphenol A alkylene oxide-modified di(meth)acrylate, isocyanuric acid alkylene oxide-modified di(meth)acrylate and polyalkylene glycol di(meth)acrylate can be cited, among which polyalkylene glycol di(meth)acrylate is preferred. The average repeating unit of the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably 3 to 5. In addition, the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably ethylene glycol and / or polyethylene glycol.
[0148] Examples of the (meth)acrylate compound having three ethylenically unsaturated bond groups modified with alkylene oxide include trimethylolpropane alkylene oxide-modified tri(meth)acrylate and isocyanuric acid alkylene oxide-modified tri(meth)acrylate.
[0149] The above-mentioned ionizing radiation curable resins may be used alone or in combination of two or more.
[0150] (Elemental analysis of the surface area of the low refractive index layer)
[0151] Preferably, the low refractive index layer contains a binder resin and silica particles, the ratio of Si element attributable to the silica particles obtained by analyzing the surface area of the low refractive index layer by X-ray photoelectron spectroscopy is greater than 10.0 atomic % and less than 18.0 atomic %, and the ratio of C element when the ratio of Si element is converted to 100 atomic % is greater than 180 atomic % and less than 500 atomic %.
[0152] In this structure, the low refractive index layer is more preferably an antifouling low refractive index layer. In addition, in this structure, the silica particles preferably include hollow silica particles and non-hollow silica particles.
[0153] If the surface of the low refractive index layer is analyzed by X-ray photoelectron spectroscopy (hereinafter referred to as "XPS"), at least C element, O element and Si element are detected. Si element comes from organic components such as silica particles (inorganic component) and silane coupling agent or leveling agent. C element comes from binder resin, surface treatment agent (silane coupling agent) of silica particles, and additives. However, if the content in the low refractive index layer is considered, C element can be regarded as substantially coming from binder resin.
[0154] In the surface area of the low refractive index layer analyzed by XPS, the ratio of the Si element attributed to the silica particles is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of the C element when the ratio of the Si element is converted to 100 atomic % is shown to be 180 atomic % or more and 500 atomic % or less. In addition, in this specification, "surface area" refers to the range of the detection area based on X-ray photoelectron spectroscopy, indicating the area from the surface of the release substrate 2 side to a depth of 10 nm in the low refractive index layer (the area from the surface of the low refractive index layer on the opposite side to the adherend to a depth of 10 nm).
[0155] "The ratio of the C element when the ratio of the Si element is converted to 100 atomic %" can be calculated by "C / Si×100(%)". Hereinafter, "the ratio of the C element when the ratio of the Si element is converted to 100 atomic %" may be abbreviated as "C / Si". In addition, Si under consideration in this specification refers to the inorganic Si element belonging to the silica particles, so even if there is no special description, Si refers to the inorganic Si element.
[0156] The above C / Si in the surface region of the low refractive index layer reflects the distribution state of the non-hollow silica particles and the hollow silica particles in the thickness direction of the low refractive index layer.
[0157] In the case where the silica particles are biased toward the side opposite to the surface of the low refractive index layer, the ratio of the Si element belonging to the silica particles in the surface region is low, and the ratio of the C element is relatively high. Even if the silica particles are buried in the binder resin and are hardly present on the surface of the low refractive index layer, the same tendency is present. On the other hand, in the case where the silica particles (particularly hollow silica particles) are not coated with the binder resin and exposed on the surface of the low refractive index layer or the coating of the binder resin is very thin and becomes close to the exposed state, the ratio of the Si element belonging to the silica particles is high, and the ratio of the C element is relatively low.
[0158] The ratio of the Si element attributed to the silica particles in the surface region of the low refractive index layer reflects the presence of the non-hollow silica particles and the hollow silica particles in the surface region.
[0159] Even if it is present in a large amount in the surface area of the low refractive index layer, since the hollow silica is a hole, it does not contribute much to the increase in the ratio of the Si element belonging to the silica particles, but when non-hollow silica is present in a large amount in the surface area, the ratio of the Si element belonging to the silica particles becomes high. By having silica particles in a sufficient amount in the surface area of the low refractive index layer, the ratio of the Si element belonging to the silica particles in the surface area of the low refractive index layer satisfies more than 10.0 atomic %. In particular, by making the ratio of the Si element belonging to the silica particles more than 13.0 atomic %, non-hollow silica particles are present in the surface side at a high concentration, and wear resistance is improved, so it is preferred. On the other hand, when the ratio of the Si element belonging to the silica particles exceeds 18.0 atomic %, not only non-hollow silica but also hollow silica particles are present in a large amount in the surface area, becoming a state where the silica particles are exposed on the surface or close to being exposed, so there is a tendency to reduce wear resistance as described later.
[0160] In addition, by having silica particles in sufficient amount in the surface area of the low refractive index layer, C / Si satisfies 500 atomic % or less. If C / Si exceeds 500 atomic %, the silica particles are buried in the binder resin, and in the surface area, the binder resin becomes too much, and there is a tendency for the wear resistance to decrease. On the other hand, if C / Si is less than 180 atomic %, the amount of silica particles present on the surface becomes more, and in particular, hollow silica particles that are not coated with the binder resin or hollow silica particles that are coated with very thin binder resin become exposed to the surface or close to the exposed state, thereby there is a tendency for the wear resistance to decrease. When considering wear resistance and sufficient coating, C / Si is preferably more than 200 atomic %, more preferably more than 250 atomic %. In addition, C / Si is preferably less than 400 atomic %, more preferably less than 350 atomic %.
[0161] By setting the ratio of the C element and the Si element in the surface region of the low refractive index layer to the above range, the hollow silica particles can be coated with an appropriate amount of binder resin and a sufficient amount of non-hollow silica particles can be present in the gaps between the hollow silica particles. Thus, the surface of the low refractive index layer can be made smoother and low in reflectivity, and it is easy to make the surface resistance such as high wear resistance good.
[0162] In addition, even if the coating liquid for forming the low refractive index layer does not contain a fluorine-containing compound such as a fluorine-based leveling agent, fluorine may sometimes be detected on the surface of the low refractive index layer after formation. For example, it is conceivable that the other functional layer adjacent to the low refractive index layer contains a fluorine-based leveling agent, and the leveling agent of the other functional layer is transferred to the surface of the low refractive index layer.
[0163] In the present embodiment, as long as in the scope that does not hinder the effect of the present invention, also can detect the F element by XPS, but preferably do not detect the F element by XPS.That is, the surface area of low-refractive index layer preferably does not contain fluorine atoms in fact.There is a softer tendency in fluorinated compound itself, therefore by making the surface area of low-refractive index layer do not contain fluorine atoms in fact, can easily make good wear resistance.
[0164] Even if the other functional layers adjacent to the low refractive index layer contain a fluorine-based leveling agent, the diffusion of the fluorine-containing compound in the other functional layers can be suppressed by making the low refractive index layer show the above-mentioned element ratio and containing silica particles at a high concentration relative to the binder resin, thereby easily achieving a state in which substantially no F atoms are contained in the surface region of the low refractive index layer.
[0165] In the present specification, “substantially containing no fluorine atoms” means that the ratio of the F element in the surface region is 0.5 atomic % or less, more preferably 0.1 atomic % or less.
[0166] It is also preferable that the surface region of the low refractive index layer has the above-mentioned element ratio because high gas barrier properties (water vapor permeability, oxygen permeability) can be imparted.
[0167] In order to achieve the above-mentioned element ratio, the low refractive index layer is preferably uniformly dispersed with hollow silica particles and non-hollow silica particles. "Uniformly dispersed" in this specification not only means that hollow silica particles and non-hollow silica particles are uniformly dispersed in the surface area of the low refractive index layer, but also means that they are also uniformly dispersed in the thickness direction of the low refractive index layer when cross-sectional observation is performed. That is, when XPS analysis is performed in the thickness direction of the low refractive index layer, the ratio of the Si element and C / Si belonging to the silica particles preferably meet the above-mentioned range at different positions in the thickness direction. For example, when the thickness of the low refractive index layer is divided into three equal parts and defined as the first region, the second region and the third region in sequence from the transparent substrate side, for any position in the first region and any position in the second region, the ratio of the Si element and C / Si belonging to the silica particles also preferably meet the above-mentioned range.
[0168] Figure 6 A cross-sectional photograph showing a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed, Figure 7 This is a cross-sectional photograph of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed.
[0169] The surface of the low refractive index layer in which hollow silica particles and non-hollow silica particles are uniformly dispersed is also preferred in that antifouling properties can be easily improved.
[0170] (Leveling agent)
[0171] From the viewpoint of antifouling property and surface smoothness, the low refractive index layer preferably contains a leveling agent. These leveling agents are preferably leveling agents having a reactive group such as a (meth)acryloyl group and capable of reacting with the binder resin.
[0172] Leveling agent can be fluorine-based and silicone-based, but silicone-based is preferred. By containing silicone-based leveling agent, the surface of the low refractive index layer can be made smoother. And then, compared with fluorine-based, silicone-based can easily make the sliding property and antifouling property (fingerprint wiping property, large contact angle relative to pure water and hexadecane) of the surface of the low refractive index layer good. In addition, compared with fluorine-based, silicone-based is preferred in terms of the hardness of the low refractive index layer that is not easily damaged.
[0173] The content of the leveling agent is preferably 1 to 25 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 5 to 18 parts by mass, based on 100 parts by mass of the binder resin.
[0174] By making the content of the leveling agent 1 part by mass or more, various properties such as antifouling property can be easily imparted. In addition, by making the content of the leveling agent 25 parts by mass or less, a decrease in abrasion resistance can be suppressed.
[0175] In order to obtain excellent surface tolerance, the low refractive index layer is preferably a smooth surface. The maximum height roughness Rz is 110nm or less, preferably 100nm or less, and more preferably 90nm or less. In addition, if it is a smoother surface, a more excellent surface tolerance can be obtained, so Rz is preferably 70nm or less, more preferably 60nm or less, and more preferably 55nm or less.
[0176] Furthermore, Rz / Ra (Ra is the arithmetic mean roughness) is preferably 22.0 or less, more preferably 18.0 or less, more preferably 16.0 or less, more preferably 12.0 or less, more preferably 10.0 or less, and more preferably 9.0 or less.
[0177] In this specification, Ra and Rz are values obtained by expanding the roughness of the two-dimensional roughness parameter described in the Scanning Probe Microscope SPM-9600 Upgrade Kit Operating Instructions (SPM-9600 February 2016, P.194-195) into three dimensions. Ra and Rz are defined as follows.
[0178] (Arithmetic mean roughness Ra)
[0179] From the roughness curve, only the reference length (L) is extracted in the direction of its average line. The direction of the average line of the extracted part is taken as the X-axis, and the direction of the longitudinal magnification is taken as the Y-axis. When the roughness curve is represented by y=f(x), the following formula is used to calculate.
[0180] [Formula 1]
[0181]
[0182] (Maximum height roughness Rz)
[0183] This is a value obtained by extracting a reference length from the roughness curve in the direction of the average line thereof and measuring the interval between the top line and the bottom line of the valley of the extracted portion in the direction of the longitudinal magnification of the roughness curve.
[0184] A small Rz means that the convex portion caused by the hollow silica particles in the micro region is small. In addition, a small Rz / Ra means that the concavity and convexity caused by the silica particles in the micro region are uniform and do not have concavities and convexities that protrude relative to the average elevation difference of the concavity and convexity. In addition, the value of Ra is not particularly limited, but is preferably 15 nm or less, more preferably 12 nm or less, further preferably 10 nm or less, and further preferably 6.5 nm or less.
[0185] By making the low refractive index particles in the low refractive index layer uniformly disperse or suppressing the shrinkage unevenness of the low refractive index layer, it is easy to satisfy the scope of above-mentioned Rz and Rz / Ra. In addition, by making the low refractive index layer show the above-mentioned element ratio, it is easy to satisfy the scope of above-mentioned Rz and Rz / Ra.
[0186] Depending on the processing conditions of the low refractive index layer, the Rz of the surface of the low refractive index layer may increase to about 90 to 110 nm. In this case, when Rz / Ra is within the above range, a preferred surface resistance is easily obtained.
[0187] By making Rz and Rz / Ra on low-refractive index layer surface in the above-mentioned range, the resistance when solids cross the convex portion (caused by the hollow silica particles present near the surface) on low-refractive index layer surface can be reduced. Therefore, it can be expected that even if the grit with oil content is used to apply load and wipe, solids also can move smoothly on the low-refractive index layer surface. In addition, it is believed that the hardness of recessed portion itself has also been improved. As a result, it can be inferred that the damage, the coming off of hollow silica particles are prevented, and the damage of binder resin itself is also prevented.
[0188] Furthermore, by setting Rz and Rz / Ra to be within the above ranges, antifouling properties can be easily improved.
[0189] On the other hand, when Rz and Rz / Ra on the surface of the low refractive index layer are too small, sometimes adhesion occurs during the manufacturing process. Therefore, Rz is preferably more than 30nm, more preferably more than 70nm. In addition, Rz / Ra is preferably more than 3.0, more preferably more than 5.0.
[0190] In this specification, various parameters such as surface roughness such as Rz and Ra, optical properties such as reflectance Y value, element ratio, etc., unless otherwise specified, refer to the average value of the measurement values of 16 locations after excluding the minimum and maximum values.
[0191] In this specification, regarding the above-mentioned 16 measurement positions, it is preferred that the area 0.5 cm from the outer edge of the measurement sample is used as a blank, and about the area inside the blank, a line that divides the longitudinal and transverse directions into 5 equal parts is drawn, and the 16 positions of the intersection at this time are used as the center of measurement. For example, in the case where the measurement sample is a quadrilateral, it is preferred that the area 0.5 cm from the outer edge of the quadrilateral is used as a blank, and the area inside the blank is divided into 5 equal parts in the longitudinal and transverse directions, and the 16 positions of the intersection of the dotted lines obtained by the 5 equal divisions are measured as the center, and the parameters are calculated using the average value. In addition, in the case where the measurement sample is a shape other than a quadrilateral, such as a circle, an ellipse, a triangle, a pentagon, etc., it is preferred to draw a quadrilateral inscribed with these shapes, and measure the 16 positions of the quadrilateral by the above method.
[0192] In addition, various parameters such as surface roughness are measured at a temperature of 23°C ± 5°C and a relative humidity of 40 to 65% unless otherwise specified. In addition, unless otherwise specified, the measurement and evaluation are performed after the target sample is exposed to the above atmosphere for more than 30 minutes before starting each measurement.
[0193] The low refractive index layer can be formed by applying a low refractive index layer-forming coating solution and drying it, wherein the low refractive index layer-forming coating solution is formed by dissolving or dispersing the components constituting the low refractive index layer. Usually, a solvent is used in the coating solution in order to adjust the viscosity or to dissolve or disperse the components.
[0194] Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), glycol ethers (1-methoxy-2-propyl acetate, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc., and mixtures thereof may also be used.
[0195] When the volatilization of the solvent is too fast, when the coating liquid for forming the low refractive index layer is dried, the solvent is violently convected. Therefore, even if the silica particles in the coating liquid are in a uniformly dispersed state, the uniformly dispersed state is easily destroyed due to the violent convection of the solvent during drying. Therefore, as a solvent, it is preferred to include a solvent with a slow evaporation rate. Specifically, it is preferred to include a solvent with a relative evaporation rate (relative evaporation rate when the evaporation rate of n-butyl acetate is set to 100) of 70 or less, and more preferably include a solvent with a relative evaporation rate of 30 to 60. In addition, the solvent with a relative evaporation rate of 70 or less is preferably 10 to 50% by mass of all solvents, and more preferably 20 to 40% by mass.
[0196] Examples of relative evaporation rates of solvents having relatively slow evaporation rates are as follows: isobutyl alcohol is 64, 1-butanol is 47, 1-methoxy-2-propyl acetate is 44, ethyl cellosolve is 38, and cyclohexanone is 32.
[0197] The remaining solvent (solvent other than the solvent with a slow evaporation rate) is preferably a component with excellent solubility in the resin. The remaining solvent is preferably a component with a relative evaporation rate of 100 or more.
[0198] In addition, in order to suppress the convection of the solvent during drying and improve the dispersibility of the silica particles, the drying temperature when forming the low refractive index layer is preferably as low as possible. The drying temperature can be appropriately set in consideration of the type of solvent, the dispersibility of the silica particles, the production speed, etc.
[0199] As described above, it is preferable to control the relative evaporation rate and the drying temperature of the solvent in order to contribute to smoothening the surface of the low refractive index layer.
[0200] ―High refractive index layer―
[0201] The refractive index of the high refractive index layer as an example of the functional layer is preferably 1.53 to 1.85, more preferably 1.54 to 1.80, more preferably 1.55 to 1.75, and more preferably 1.56 to 1.70.
[0202] The thickness of the high refractive index layer is preferably 200 nm or less, more preferably 50 to 180 nm, and even more preferably 70 to 150 nm. In the case of a high refractive index hard coat layer, the thickness of the hard coat layer is preferably used as a reference.
[0203] The high refractive index layer can be formed, for example, from a high refractive index layer-forming coating liquid containing a binder resin composition and high refractive index particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0204] Examples of high refractive index particles include antimony pentoxide (1.79), zinc oxide (1.90), titanium oxide (2.3-2.7), cerium oxide (1.95), tin-doped indium oxide (1.95-2.00), antimony-doped tin oxide (1.75-1.85), yttrium oxide (1.87) and zirconium oxide (2.10).
[0205] The average particle size of the high refractive index particles is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. In addition, from the viewpoint of suppressing whitening and transparency, the average particle size of the high refractive index particles is preferably less than 200nm, more preferably less than 100nm, more preferably less than 80nm, more preferably less than 60nm, and more preferably less than 30nm. The smaller the average particle size of the high refractive index particles, the better the transparency, and particularly by being set to less than 60nm, the transparency can be made very good.
[0206] The average particle diameter of the high refractive index particles and the low refractive index particles can be calculated by the following operations (y1) to (y3).
[0207] (y1) Taking a cross-section of the high refractive index layer or the low refractive index layer by TEM or STEM The accelerating voltage of TEM or STEM is preferably 10 kV to 30 kV, and the magnification is preferably 50,000 to 300,000 times.
[0208] (y2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in a combination of two straight lines that is the maximum distance between the two straight lines when the cross section of the particle is sandwiched between the two straight lines. In the case of particle aggregation, the aggregated particles are measured as one particle.
[0209] (Y3) The same operation is performed five times on another observation image of the same sample, and the value obtained by averaging the numerical values of 50 particle sizes in total is set as the average particle size of the high refractive index particles or the low refractive index particles.
[0210] - Anti-glare layer -
[0211] The anti-glare layer, which is an example of the functional layer, has a function of improving the anti-glare property of an adherend.
[0212] The anti-glare layer can be formed by, for example, an anti-glare layer-forming coating solution comprising a binder resin composition and particles. In addition, it can also be formed by utilizing phase separation of a resin composition, or by making a resin composition utilizing such phase separation contain particles to form. As the binder resin composition, for example, a curable resin composition exemplified in the hard coat layer can be used.
[0213] The particles may be either organic particles or inorganic particles. Examples of organic particles include particles made of polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine resin, polyester resin, etc. Examples of inorganic particles include particles made of silicon dioxide, aluminum oxide, antimony, zirconium oxide, titanium dioxide, etc.
[0214] The average particle size of the particles in the antiglare layer cannot be generally determined because it varies depending on the thickness of the antiglare layer, but is preferably 1.0 to 10.0 μm, more preferably 2.0 to 8.0 μm, and further preferably 3.0 to 6.0 μm.
[0215] The average particle size of the particles in the antiglare layer can be calculated by the following operations (z1) to (z3).
[0216] (z1) Taking a transmission observation image of the cross section of the anti-glare layer using an optical microscope. The magnification is preferably 500 to 2000 times.
[0217] (z2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in a combination of two straight lines that is the maximum distance between the two straight lines when the cross section of the particle is sandwiched between the two straight lines.
[0218] (z3) The same operation is performed five times on another observed image of the same sample, and the value obtained by averaging the numerical values of the particle diameters of 50 in total is defined as the average particle diameter of the particles in the antiglare layer.
[0219] The content of the particles in the antiglare layer varies depending on the desired degree of antiglare properties and cannot be determined without specification, but is preferably 1 to 100 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 10 to 30 parts by mass based on 100 parts by mass of the resin component.
[0220] Furthermore, the anti-glare layer may contain fine particles having an average particle size of less than 500 nm in order to impart antistatic properties, control the refractive index, or adjust the shrinkage of the anti-glare layer caused by curing of the curable resin composition.
[0221] The thickness of the antiglare layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, the thickness of the antiglare layer is preferably 50 μm or less, more preferably 30 μm or more, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less.
[0222] - Antifouling layer -
[0223] The antifouling layer as an example of the functional layer has a function of improving the antifouling property of the adherend. When the transfer layer has two or more functional layers, the antifouling layer is preferably formed on the side farthest from the release substrate 1 .
[0224] The antifouling layer can be formed, for example, from an antifouling layer-forming coating liquid containing a binder resin composition and an antifouling agent. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0225] Examples of the antifouling agent include fluorine-based resins, silicone-based resins, and fluorine-silicone copolymer resins.
[0226] In order to suppress bleeding from the antifouling layer, the antifouling agent preferably has a reactive group capable of reacting with the binder resin composition. In other words, in the antifouling layer, the antifouling agent is preferably fixed to the binder resin composition.
[0227] Furthermore, from the viewpoint of suppressing bleeding from the antifouling layer, an antifouling agent that can self-crosslink is also preferred. In other words, in the antifouling layer, the antifouling agent is preferably self-crosslinked.
[0228] The content of the antifouling agent in the antifouling layer is preferably 5 to 30% by mass, more preferably 7 to 20% by mass, based on the total solid content of the antifouling layer.
[0229] The thickness of the antifouling layer is not particularly limited. For example, when an antifouling hard coat is used, the thickness of the hard coat is preferably used as a benchmark. In addition, when an antifouling low-refractive index layer is used, the thickness of the low-refractive index layer is preferably used as a benchmark.
[0230] The degree of antifouling property of the antifouling layer varies depending on the required antifouling property and cannot be generally determined, but the contact angle of pure water is preferably 80 degrees or more, more preferably 85 degrees or more, and even more preferably 90 degrees or more.
[0231] If the contact angle of pure water of the antifouling layer becomes too large, the content of the antifouling agent in the antifouling layer may increase relatively, thereby reducing the physical properties (abrasion resistance, etc.) of the antifouling layer. Therefore, the contact angle of pure water of the antifouling layer is preferably 120 degrees or less, more preferably 110 degrees or less, further preferably 100 degrees or less, and further preferably 95 degrees or less.
[0232] When other functional layers such as the low refractive index layer have antifouling properties, the contact angle of pure water is also preferably within the above range.
[0233] In this specification, the contact angle is measured by the θ / 2 method.
[0234] -Layer on the side farthest from the release substrate 2-
[0235] When the adherend is glass, the layer on the side farthest from the release substrate 2 among the layers constituting the transfer layer preferably contains a resin having one or more functional groups selected from a carboxyl group and a methoxy group. By making the layer contain a resin having one or more functional groups selected from a carboxyl group and a methoxy group, it is easy to make the adhesion with glass good.
[0236] The proportion of the resin having one or more functional groups selected from carboxyl and methoxy in the total resin components of the layer is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass.
[0237] <Step (2)>
[0238] Step (2) is the following step: laminating a release substrate 2 on the transfer layer formed in step (1) to obtain a transfer sheet A which has a release substrate 1, a transfer layer and a release substrate 2 in sequence, and in which the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer.
[0239] In step (2), the means for laminating the release substrate 2 on the transfer layer is not particularly limited. For example, the release substrate 2 can be laminated on the transfer layer by dry lamination.
[0240] When the release substrate 2 has an adhesive layer, the adhesive force of the adhesive layer can be used to dry-laminate the release substrate 2 on the transfer layer. In addition, when the functional layer at the farthest position from the release substrate 1 among the functional layers constituting the transfer layer has adhesiveness at the time of step (2), the release substrate 2 can be dry-laminated on the transfer layer by using the adhesiveness of the functional layer.
[0241] Of the two release substrates included in the transfer sheet A, release substrate 1 is peeled off before transfer and does not remain during transfer, but release substrate 2 remains during transfer. In order to allow only release substrate 1 to be peeled off before transfer, in step (2), the peel strength 2 between release substrate 2 and the transfer layer needs to be greater than the peel strength 1 between release substrate 1 and the transfer layer.
[0242] In addition, as shown in Comparative Example 4-1, if a starting point for peeling is provided by generating a cut or the like and the transfer sheet is pressed from both sides, the release substrate 1 can be peeled off first even if the relationship of "peel strength 2 < peel strength 1" is satisfied. However, in the case of the relationship of "peel strength 2 < peel strength 1", the transfer process is significantly complicated, and a load is applied to the transfer layer during transfer, which may impair the function of the transfer layer, and therefore, this is not preferred.
[0243] From the viewpoint of easily peeling off the release substrate 1 before transfer, the difference between the peel strength 2 and the peel strength 1 (peel strength 2-peel strength 1) is preferably 15 mN / 25 mm or more, more preferably 40 mN / 25 mm or more, and further preferably 100 mN / 25 mm or more. In addition, if the difference is too large, it may be difficult to peel off the release substrate 2 after transfer, so the difference is preferably 450 mN / 25 mm or less, more preferably 350 mN / 25 mm or less, further preferably 300 mN / 25 mm or less, and further preferably 200 mN / 25 mm or less.
[0244] From the viewpoint of suppressing the falling off of the release substrate 1, the peel strength 1 is preferably 10 mN / 25 mm or more, more preferably 20 mN / 25 mm or more, further preferably 40 mN / 25 mm or more, and further preferably 50 mN / 25 mm or more. In addition, from the viewpoint of easily generating a difference with the peel strength 2, the peel strength 1 is preferably 90 mN / 25 mm or less, and more preferably 70 mN / 25 mm or less.
[0245] From the viewpoint of easily generating a difference from the peel strength 1, the peel strength 2 is preferably 100 mN / 25 mm or more, more preferably 120 mN / 25 mm or more, and further preferably 140 mN / 25 mm or more. In addition, from the viewpoint of suppressing the cohesive failure of the adhesive layer and the transfer layer on the release substrate 2 side when the release substrate 2 is peeled, the peel strength 2 is preferably 600 mN / 25 mm or less, more preferably 500 mN / 25 mm or less, further preferably 400 mN / 25 mm or less, and further preferably 300 mN / 25 mm or less.
[0246] In this specification, the peel strength can be measured according to the 180 degree peel test of JIS Z0237:2009. In addition, the atmosphere for measuring the peel strength is preferably set to 23°C and a humidity of 40 to 65%. In addition, before measuring the peel strength, it is preferred to acclimate the sample in the above atmosphere for 30 minutes. For one sample, three measurements are performed, and the average value is set as the peel strength.
[0247] <<Release substrate 2>>
[0248] The release substrate 2 can be used without particular limitation as long as it can be peeled from the transfer layer, but a plastic film is preferably used.
[0249] As the plastic film used as the release substrate 2 , the same plastic films as those exemplified in the plastic film of the release substrate 1 can be used.
[0250] The transfer layer-side surface of the release substrate 2 preferably has an arithmetic mean roughness Ra of 0.04 μm or less in accordance with JIS B0601:1994 at a cutoff value of 0.25 mm. Ra of the release substrate 2 can be measured by the same method as Ra of the release substrate 1 .
[0251] In addition, although the release substrate 1 is peeled off before transfer and does not remain during transfer, the release substrate 2 remains during transfer. Therefore, with respect to the release substrate 2, it is preferred that the shape followability relative to the adherend is good. Specifically, the elongation at break of the release substrate 2 obtained by the tensile property test in accordance with JIS K7127:1999 is preferably 70% or more, and more preferably 80% or more. In addition, in the case where the release substrate 2 is easily elongated, after the release substrate 2 is stacked on the transfer layer, a force to shrink is generated on the release substrate 2, so that the release substrate 1 is easily peeled off from the transfer layer. Therefore, when using a substrate that is easily elongated as the release substrate 2, it is preferred to increase the peel strength 1 (preferably 40mN / 25mm or more, more preferably 50mN / 25mm or more).
[0252] From the viewpoint of making the peel strength 2 greater than the peel strength 1 and being able to be peeled from the transfer layer, the release substrate 2 preferably has a weak adhesive layer on the surface.
[0253] The adhesive contained in the adhesive layer on the surface of the release substrate 2 preferably has a weak adhesive force such that the peel strength 2 falls within the above range.
[0254] From the viewpoint of suppressing peeling static electricity, the release substrate 2 preferably has an antistatic layer.
[0255] Although the thickness of the release substrate 2 is not particularly limited, it is preferably 5 to 100 μm, more preferably 10 to 80 μm, and even more preferably 20 to 70 μm from the viewpoint of operability after peeling off the release substrate 1 and shape followability of the adherend. In addition, since the transfer sheet B becomes soft as a whole and is easy to use for transfer to a 3D form, the upper limit is more preferably 60 μm or less, and most preferably 45 μm or less.
[0256] The effects of the transfer sheet A obtained by the method for producing a transfer sheet of the present invention will be described below.
[0257] The transfer sheet A was used as follows.
[0258] First, before transfer, the release substrate 1 is peeled off from the transfer sheet A to obtain Figure 3 The transfer sheet B (200) shown in FIG. Figure 4 As shown in (a), after obtaining a laminated body C (400) in which the transfer layer side of the transfer sheet B is in close contact with the adherend, Figure 4 As shown in (b) , the release substrate 2 is peeled off from the laminate C, thereby obtaining a molded body 800 in which the transfer layer is transferred to the adherend.
[0259] Figure 4 The orientation of the functional layer 1 (31) and the functional layer 2 (32) in the thickness direction of (b) is Figure 1 The functional layer 1 (31) and the functional layer 2 (32) of the transfer layer are oriented in the same direction in the thickness direction. In other words, Figure 4 The upper side of the functional layer 1 (31) and the functional layer 2 (32) in the thickness direction of (b) is Figure 1 The upper sides of the functional layer 1 (31) and the functional layer 2 (32) in the thickness direction are in the same direction.
[0260] When a functional layer is formed on any substrate, the function may be roughly uniform in the thickness direction of the functional layer, but in most cases, the function is biased in the thickness direction of the functional layer. In other words, the surface side of the functional layer and the substrate side of the functional layer often have different functions. Moreover, conventional functional coatings are designed to fully exert their functions on the surface side of the functional layer. Therefore, Figure 4 The upper side of the functional layer 1 (31) and the functional layer 2 (32) in the thickness direction of (b) is Figure 1 The fact that the upper sides of the thickness directions of the functional layer 1 (31) and the functional layer 2 (32) are in the same direction means Figure 4 The functional layer of the molded body (b) is easy to fully exert its function. For example, Figure 1 and Figure 4 The functional layer 2 (32) of (b) is that the functional components are biased toward the surface side ( Figure 1 and Figure 4 (b) (the darker the color of the functional layer 2 (32), the higher the density of the functional components and the more concentrated the functional components are), and the functional layer 2 (32) is a functional layer that can fully exert its functions.
[0261] On the other hand, conventional transfer sheets are made of, for example, Figure 5 A cross-sectional structure as shown in (a) is formed. Figure 5 The conventional transfer sheet of (a) has a transfer layer 30 on a release substrate 13 , and the transfer layer 30 has a functional layer 2 ( 32 ) and a functional layer 1 ( 31 ) from the release substrate side.
[0262] In addition, regarding the conventional transfer sheet, Figure 5 After obtaining a laminated body in which the transfer layer side of the transfer sheet is in close contact with the adherend as in (b), Figure 5 By peeling the release substrate 13 from the laminate as in (c), a molded body 800 in which the transfer layer is transferred to the adherend is obtained.
[0263] Figure 5 The orientation of the functional layer 1 (31) and the functional layer 2 (32) in the thickness direction of (c) is Figure 5 The functional layer 1 (31) and the functional layer 2 (32) of the transfer layer of (a) are oriented differently in the thickness direction. In other words, Figure 5 The functional layer 1 (31) and the functional layer 2 (32) of (c) correspond to the upper side in the thickness direction. Figure 5 The functional layer 1 (31) and the functional layer 2 (32) of (a) are on the lower side in the thickness direction.
[0264] Thus, in the transfer based on the conventional transfer sheet, the thickness direction of the functional layer formed on the release substrate and the thickness direction of the functional layer transferred to the adherend are reversed, so it is difficult for the functional layer to fully function. Figure 5 The functional components of the functional layer 2 (32) of the molded body 800 of (c) are biased toward the side opposite to the surface ( Figure 5 ) on the lower side of (c), so the functional layer 2 (32) cannot fully function.
[0265] As described above, according to the transfer sheet A obtained by the method for producing a transfer sheet of the present invention, sufficient functions can be imparted to a molded body.
[0266] In addition, the above-mentioned functional bias is very significant when the functional layer is an anti-glare layer or an anti-fouling layer. Therefore, the method for manufacturing the transfer sheet of the present invention is preferred in the following aspects: when at least one of the functional layers is an anti-glare layer or an anti-fouling layer, the effect is more easily exerted. In particular, at least one of the functional layers is preferably an anti-fouling low refractive index layer.
[0267] On the other hand, in the case of the structure of the conventional transfer sheet, even if the transfer layer includes an antiglare layer and an antifouling layer, sufficient antiglare and antifouling properties cannot be imparted to an adherend for the following reasons.
[0268] First, in the case where the conventional transfer sheet includes an anti-glare layer as the transfer layer, the surface shape of the anti-glare layer transferred to the adherend has a shape that is substantially complementary to the surface shape of the release sheet. Furthermore, in order to improve the release property from the transfer layer, the surface shape of the release sheet is usually smoothed, so the surface shape of the anti-glare layer transferred to the adherend does not have a concave-convex shape, and cannot provide sufficient anti-glare properties. For example, when using Figure 5 In the case where the functional layer 2 (32) of (a) is an antiglare layer and the functional layer 1 (31) is an adhesive layer, Figure 5 The surface shape of the functional layer 2 (32, anti-glare layer) of (c) becomes a shape complementary to the surface shape of the release substrate 13, and it is difficult to impart anti-glare properties based on surface irregularities.
[0269] Furthermore, when an antifouling layer containing an antifouling agent is formed on a substrate, the antifouling agent tends to aggregate at an air interface having a low surface energy. Figure 5 In the case where the functional layer 2 (32) of (a) is an antifouling layer and the functional layer 1 (31) is an adhesive layer, Figure 5 The ratio of the functional component (antifouling agent) on the surface side of the functional layer 2 (32, antifouling layer) (c) is low, and sufficient antifouling property cannot be imparted.
[0270] <Step (3)>
[0271] The method for producing a transfer sheet of the present invention preferably further comprises the following step (3).
[0272] (3) A step of peeling the release substrate 1 from the transfer sheet A to obtain a transfer sheet B having the transfer layer on the release substrate 2 .
[0273] In step (3), the release substrate 1 is peeled off from the transfer sheet A obtained in step (2).
[0274] The release substrate 1 also has the function of protecting the transfer layer when the transfer sheet is cut or transported, but is a material not required during transfer. Therefore, as shown in step (3), the release substrate 1 is preferably peeled off before transfer.
[0275] [Method for producing molded article]
[0276] In the method for producing a molded article of the present invention, the following steps (4) to (5) are performed in order.
[0277] (4) A step of obtaining a laminated body C in which the surface of the transfer layer side of the transfer sheet B is in close contact with an adherend.
[0278] (5) A step of peeling the release substrate 2 from the laminate C to obtain a molded body having a transfer layer on an adherend.
[0279] Step (4) is a step of obtaining a laminated body C (400) in which the surface of the transfer layer side of the transfer sheet B is in close contact with the adherend. Figure 4 (a)).
[0280] In step (4), the means for bringing the surface of the transfer layer side of the transfer sheet B into close contact with the adherend is not particularly limited. For example, when the layer located at the position farthest from the peeling substrate 2 among the layers constituting the transfer layer shows adhesion (preferably thermosensitive adhesion), the adhesion of the layer can be used to bring the transfer layer into close contact with the adherend. In addition, in the case of in-mold molding, the transfer layer can be brought into close contact with the adherend by using a resin with high adhesion to the transfer layer as an injection resin (≈ adherend). In addition, the transfer layer can also be brought into close contact with the adherend by means of a double-sided adhesive sheet.
[0281] <Adhesive>
[0282] The material of the adherend is not particularly limited, and examples thereof include one selected from inorganic materials such as glass and ceramics, and resins, or a mixture thereof.
[0283] When in-mold molding is performed, as the adherend, an injection-moldable thermoplastic resin or a thermosetting resin is preferably used, and among them, a thermoplastic resin is more preferred.
[0284] Examples of the thermoplastic resin include polystyrene resins, polyolefin resins, ABS resins (including heat-resistant ABS resins), AS resins, AN resins, polyphenylene ether resins, polycarbonate resins, polyacetal resins, acrylic resins, polyethylene terephthalate resins, polybutylene terephthalate resins, polysulfone resins, and polyphenylene sulfide resins.
[0285] Furthermore, the shape of the adherend is not particularly limited, and may be a flat plate or a three-dimensional shape. Furthermore, the thickness of the adherend is not particularly limited.
[0286] The adherend may be a preformed adherend or an adherend formed during the step (4) such as in-mold molding.
[0287] Step (5) is a step of peeling the release substrate 2 (20) from the laminate C (400) to obtain a molded body having the transfer layer 30 on the adherend 300 ( Figure 4 (b)).
[0288] In steps (4) and (5), a known transfer method can be used.
[0289] For example, the following methods can be cited: (i) a method for preparing a laminate C in which the surface of the transfer layer side of the transfer sheet B is in close contact with a pre-formed adherend, and peeling off the release substrate 2 from the laminate C; (ii) a method for preparing a laminate C in which the surface of the transfer layer side of the transfer sheet B is in close contact with a flat-plate adherend, and peeling off the release substrate 2 from the laminate C; (iii) a method for preparing a laminate C in which the adherend is integrated (in close contact) with the surface of the transfer layer side of the transfer sheet B during injection molding, and peeling off the release substrate 2 from the laminate C [in-mold molding (injection molding and simultaneous transfer decoration method)].
[0290] As one embodiment of the in-mold molding, there can be mentioned in-mold molding having the following steps (a) to (d).
[0291] (a) Step of placing the transfer layer side of the transfer sheet B toward the inside of the in-mold molding mold
[0292] (b) Step of injecting resin into the mold for in-mold molding
[0293] (c) A step of obtaining a laminated body C in which the transfer layer side surface of the transfer sheet B is integrated with (closely adhered to) the resin.
[0294] (d) Step of peeling the release substrate 2 from the laminate C after taking the laminate C out of the mold
[0295] [Transfer Sheet A]
[0296] The transfer sheet A of the present invention comprises a release substrate 1, a transfer layer and a release substrate 2 in sequence, wherein the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer, and the transfer layer comprises at least one functional layer, and at least one of the functional layers is functionally biased toward the release substrate 2 side.
[0297] The embodiments of the release substrate 1 and release substrate 2, and the peel strength 1 and peel strength 2 of the transfer sheet A of the present invention are the same as the release substrate 1 and release substrate 2, and the peel strength 1 and peel strength 2 used in the above-mentioned method for manufacturing the transfer sheet of the present invention. For example, the difference between the peel strength 2 and the peel strength 1 (peel strength 2-peel strength 1) is preferably 15mN / 25mm or more, more preferably 40mN / 25mm or more, and further preferably 100mN / 25mm or more. In addition, the difference is preferably 450mN / 25mm or less, more preferably 350mN / 25mm or less, further preferably 300mN / 25mm or less, and further preferably 200mN / 25mm or less.
[0298] The embodiment of the transfer layer of the transfer sheet A of the present invention is the same as the embodiment of the transfer layer of the method for producing a transfer sheet of the present invention described above, and the functional deviation will be further described below.
[0299] The transfer layer of the transfer sheet A of the present invention includes at least one functional layer, and at least one functional layer of the functional layer is formed by having its function biased toward the release substrate 2 side. By making the function of at least one functional layer included in the transfer layer biased toward the release substrate 2 side, the molded body obtained by peeling off the release substrate 1 to obtain the transfer sheet B and transferring the transfer layer of the transfer sheet B to the adherend can fully exert the function of the functional layer whose function is biased toward the release substrate 2 side. In the case where the functional layer is a single layer, it is sufficient to bias the function in the single layer toward the release substrate 2 side. In addition, preferably, in the case where there are two or more functional layers in the transfer layer, it is preferred that the function of the functional layer on the side closest to the release substrate 2 is biased.
[0300] As mentioned above, in the conventional transfer sheets, it is difficult to fully exert the functions of the anti-glare layer and the anti-fouling layer. Therefore, the transfer sheet A of the present invention is appropriate in the following aspects: when the functional layer formed by the function being biased toward the release substrate 2 side is an anti-glare layer or an anti-fouling layer, it is easier to exert the effect. In particular, at least one of the functional layers is preferably an anti-fouling low refractive index layer.
[0301] The distribution of functions in the functional layer can be evaluated by the concentration of the functional component, the cross-sectional shape, and the like.
[0302] For example, regarding the concentration of functional components, the concentration (X2) of the functional components contained in the functional layer at the interface with the release substrate 2 and the concentration (X1) of the functional components contained in the functional layer on the side opposite to the release substrate 2 (the interface with the release substrate 1) are compared to evaluate the functional bias. At this time, for example, X2 / X1 of 10 or more (preferably X2 / X1 of 20 or more, more preferably X2 / X1 of 50 or more) can be used as a benchmark for the function to be biased. More specifically, when the functional layer is an antifouling layer and the functional component that exerts antifouling properties is a fluorine component, the ratio of fluorine atoms in the functional layer at the interface with the release substrate 2 and the ratio of fluorine atoms in the functional layer at the interface with the release substrate 1 are quantitatively analyzed by X-ray photoelectron spectroscopy (XPS), thereby confirming that the function (antifouling properties) is biased.
[0303] In addition, the transfer layer is prepared by subjecting the molded body (for example, a molded body prepared by the method for producing a molded body of the present invention) to the same formulation of the transfer layer. Figure 4 The molded body obtained by the process of the present invention is different from the molded body obtained by the conventional method of manufacturing the molded body (for example, the molded body obtained by the process of the present invention). Figure 5 By comparing the physical properties of the molded body obtained by the process of the present invention, the partiality of the functional components can also be evaluated. The physical properties to be compared include, for example, water contact angle, pencil hardness, reflectivity, etc.
[0304] In addition, regarding the cross-sectional shape, for example, a scanning transmission electron microscope (STEM) is used to photograph the cross-section obtained by cutting the functional layer in the vertical direction, and the length (L2) of the ridgeline of the surface of the functional layer on the release substrate 2 side is compared with the length (L1) of the ridgeline of the surface of the functional layer on the side opposite to the release substrate 2 (release substrate 1 side), so that the functional bias can be evaluated. For example, in the case where the functional layer is an anti-glare layer, it can be said that the surface of the functional layer on the side with longer ridgelines is concave-convex, and the function (anti-glare property) is fully exerted, so L2 can be longer than L1 as a benchmark for the bias of the function (anti-glare property). L2 / L1 varies depending on the strength of the anti-glare property to be imparted, so it cannot be generalized, but is preferably greater than 1.001, and more preferably greater than 1.002. In addition, when the average inclination angle on the L2 side is 3 degrees and the average inclination angle on the L1 side is 0 degrees, L2 / L1 is 1.00137, and when the average inclination angle on the L2 side is 5 degrees and the average inclination angle on the L1 side is 0 degrees, L2 / L1 is 1.00382.
[0305] In addition, when the functional layer closest to the release substrate 2 among the functional layers is an anti-glare layer, the bias of the function (anti-glare property) can also be confirmed by measuring the surface shape of the anti-glare layer after transfer to the adherend. Specifically, if the arithmetic mean roughness Ra of JIS B0601:1994 at the cutoff value of 0.25 mm on the surface of the anti-glare layer is greater than 0.05 μm, it can be said that the function of the anti-glare layer is biased. In addition, if the release substrate 2 remains and the Ra on the transfer layer side is measurable, it can be said that the relationship of Ra of the release substrate 2 < Ra on the surface of the anti-glare layer holds, and the function of the anti-glare layer is biased.
[0306] The antiglare layer may be a type in which surface irregularities are imparted by particles or a type in which surface irregularities are imparted by phase separation of a resin. In the present embodiment, any type can easily make L2 / L1 fall within the above range.
[0307] The transfer sheet A may be in the form of a single sheet cut into a predetermined size, or in the form of a roll in which a long strip is wound into a roll. In addition, the size of a single sheet is not particularly limited, but the maximum diameter is about 2 to 500 inches. The "maximum diameter" refers to the maximum length when connecting any two points of the transfer sheet A. For example, when the transfer sheet A is rectangular, the diagonal of the area is the maximum diameter. In addition, when the transfer sheet A is circular, the diameter is the maximum diameter.
[0308] The width and length of the roll are not particularly limited, but generally speaking, the width is 200 to 3000 mm and the length is about 100 to 5000 m. The roll-shaped transfer sheet A can be cut into individual sheets for use according to the size of the adherend. When cutting, it is preferred to exclude the end of the roll whose physical properties are unstable.
[0309] Furthermore, the shape of the single piece is not particularly limited, and may be, for example, a polygon (triangle, quadrilateral, pentagon, etc.), a circle, or a random irregular shape.
[0310] [Transfer Sheet B]
[0311] The transfer sheet B of the present invention comprises a transfer layer on a release substrate 2 , wherein the transfer layer includes at least one functional layer, and at least one of the functional layers has a function biased toward the release substrate 2 side.
[0312] As mentioned above, in the conventional transfer sheets, it is difficult to fully exert the functions of the anti-glare layer and the anti-fouling layer. Therefore, the transfer sheet B of the present invention is preferred in the following aspects: when the functional layer formed by the function being biased toward the release substrate 2 side is an anti-glare layer or an anti-fouling layer, the effect is more easily exerted. In particular, at least one of the functional layers is preferably an anti-fouling low refractive index layer.
[0313] The transfer sheet B of the present invention can be obtained by peeling off the release substrate 1 of the transfer sheet A of the present invention described above.
[0314] [Molding body]
[0315] The molded article of the present invention comprises a transfer layer on an adherend, the transfer layer comprises at least one functional layer, and at least one of the functional layers has a function biased toward the side opposite to the adherend.
[0316] The embodiment of the adherend constituting the molded body of the present invention is the same as the embodiment of the adherend used in the above-mentioned method for producing a molded body of the present invention. For example, the adherend may be one selected from glass, ceramics and resins or a mixture thereof.
[0317] The molded body of the present invention is preferred in the following aspects: when the adherend is glass, it is easy to give the glass a sense of luxury and texture. In the case where the functional layer whose function is biased to the side opposite to the adherend is a low refractive index layer, it is easier to exert this effect. In addition, by satisfying any one of the following conditions: (a) the Si element ratio and C / Si of the low refractive index layer are in the above range; and (b) the low refractive index layer shows antifouling properties and the pure water contact angle is in the above range, thus, it is easier to exert this effect, and by satisfying both (a) and (b), it is easier to exert this effect. In recent years, due to the large-scale, narrow design of the frame (bezel), 3D shaping (especially in the continuous development of 3D shaping in vehicle-mounted use) of image display devices, the sense of luxury and texture of glass are valued, so the molded body of the present invention is useful.
[0318] In addition, the embodiment of the transfer layer constituting the molded body of the present invention is the same as the embodiment of the transfer layer used in the above-mentioned method for producing the transfer sheet of the present invention.
[0319] In addition, the transfer layer constituting the molded body of the present invention has at least one functional layer, and at least one functional layer of the functional layer is formed by functionally biasing to the side opposite to the adherend. Regarding the bias of the function, as described in the transfer sheet A of the present invention. For example, the functional layer formed by functionally biasing to the side opposite to the adherend is preferably an anti-glare layer, an anti-fouling layer or an anti-fouling low-refractive index layer. In addition, it is preferred that the anti-fouling low-refractive index layer contains an adhesive resin and silica particles, and the ratio of the Si element belonging to the silica particles obtained by analyzing the surface area of the anti-fouling low-refractive index layer by X-ray photoelectron spectroscopy is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of the C element when the ratio of the Si element is converted to 100 atomic % is 180 atomic % or more and 500 atomic % or less.
[0320] As mentioned above, it is difficult for the molded body made by using the conventional transfer sheet to fully exert the anti-glare and anti-fouling functions through the anti-glare layer and anti-fouling layer contained in the transfer layer. Therefore, the molded body of the present invention is preferred in the following aspects: when the functional layer formed by the function being biased to the side opposite to the adherend is the anti-glare layer or the anti-fouling layer, it is easier to exert the effect. In particular, at least one of the functional layers is preferably an anti-fouling low-refractive index layer.
[0321] In the molded body of the present invention, from the viewpoint of the adhesion between the adherend and the transfer layer, the layer closest to the adherend among the layers constituting the transfer layer is preferably an adhesive layer. The embodiment of the adhesive layer is the same as the embodiment of the adhesive layer exemplified in the method for manufacturing the transfer sheet of the present invention described above.
[0322] In addition, in the molded article of the present invention, it is preferred that the adherend is glass, and the layer closest to the adherend among the layers constituting the transfer layer contains a resin having one or more functional groups selected from a carboxyl group and a methoxy group. By setting such a structure, it is easy to make the adhesion between the glass as the adherend and the transfer layer good.
[0323] The proportion of the resin having one or more functional groups selected from carboxyl groups and methoxy groups in the total resin components of the layer closest to the adherend is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass.
[0324] In addition, when the material of the adherend is an acrylic resin, the layer closest to the adherend in the layers constituting the transfer layer preferably contains an acrylic resin. In addition, when the material of the adherend is any one selected from modified polyphenylene ether, polycarbonate resin and styrene resin, the layer closest to the adherend in the layers constituting the transfer layer preferably contains one or more selected from acrylic resin, polystyrene resin, polyamide resin and polyester resin. In addition, when the material of the adherend is a polypropylene resin, the layer closest to the adherend in the layers constituting the transfer layer preferably contains one or more selected from chlorinated polyolefin resin, chlorinated ethylene-vinyl acetate copolymer resin, cyclized rubber and benzofuran indene resin.
[0325] In the case where the transfer layer transferred to the adherend includes a low refractive index layer, the visual reflectance Y value measured at a light incident angle of 5 degrees from the side of the molded body having the low refractive index layer is preferably 2.0% or less, more preferably 1.0% or less, more preferably 0.5% or less, and more preferably 0.2% or less.
[0326] In this specification, the visual reflectance Y value refers to the visual reflectance Y value of the CIE 1931 standard color system. The visual reflectance Y value can be calculated using a spectrophotometer (e.g., manufactured by Shimadzu Corporation, trade name "UV-2450"). In addition, when the adherend is light-transmissive, it is preferred to prepare a sample obtained by attaching a light-shielding black plate to the back of the adherend through an adhesive layer, and measure the visual reflectance Y value of the sample.
[0327] [Front panel for image display device]
[0328] The front panel for an image display device of the present invention is composed of the above-mentioned molded article of the present invention.
[0329] The front plate of the present invention is preferably used in such a manner that the surface on the transfer layer side faces the front surface of the image display device.
[0330] The front panel is preferably in the form of a single sheet cut into a predetermined size. The size of the single sheet is not particularly limited, but the maximum diameter is about 2 to 500 inches. "Maximum diameter" refers to the maximum length when any two points of the front panel are connected. For example, when the front panel is rectangular, the diagonal of the area is the maximum diameter. In addition, when the front panel is circular, the diameter is the maximum diameter.
[0331] The shape of the single piece is not particularly limited, and may be, for example, a polygon (triangle, quadrilateral, pentagon, etc.), a circle, or a random irregular shape.
[0332] [Image display device]
[0333] The image display device of the present invention is an image display device including a display element and a front panel, wherein the front panel is the molded product of the present invention described above.
[0334] As display elements, there can be cited liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, etc., and further LED display elements such as micro LED display elements can be cited. These display elements can also have a touch panel function inside the display element.
[0335] As the display mode of the liquid crystal of the liquid crystal display element, there can be IPS mode, VA mode, multi-domain mode, OCB mode, STN mode, TSTN mode, etc. In the case where the display element is a liquid crystal display element, a backlight is required. The backlight is arranged on the side of the liquid crystal display element opposite to the side having the molded body.
[0336] The image display device may be an image display device with a touch panel.
[0337] The front plate is preferably arranged so that the surface on the transfer layer side faces the side opposite to the display element.
[0338] The size of the image display device is not particularly limited, but the maximum diameter is about 2 to 500 inches. The "maximum diameter" refers to the maximum length when connecting any two points of the image display device. For example, in the case where the image display device is rectangular, the diagonal of the area is the maximum diameter. In addition, in the case where the image display device is circular, the diameter is the maximum diameter.
[0339] The shape of the image display device is not particularly limited, and may be, for example, a polygon (triangle, quadrilateral, pentagon, etc.), a circle, or a random irregular shape.
[0340] Example
[0341] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples. In addition, the present invention is not limited to the embodiments described in the Examples.
[0342] 1. Evaluation and measurement related to functional bias
[0343] The following measurements and evaluations were performed on the molded bodies obtained in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-3. The results are shown in Table 1. The size of the molded body used in the following measurements and evaluations is only an example and is not limited thereto.
[0344] The atmosphere during each measurement and evaluation was set to a temperature of 23°C ± 5°C and a humidity of 40 to 65%. Before starting each measurement and evaluation, the molded article was exposed to the above atmosphere for 30 minutes or more before measurement and evaluation.
[0345] 1-1. Antifouling properties (water contact angle)
[0346] A glass plate with double-sided tape (751B, manufactured by Teraoka Manufacturing Co., Ltd.) was prepared by bonding a double-sided tape to a 10×10 cm soda glass. The release substrate 1 of the transfer sheet A of Examples 1-1 to 1-3 was peeled off to prepare a transfer sheet B, and a 10×10 cm laminate was obtained by bonding the adhesive layer side of the transfer sheet B to the surface of the glass plate to which the double-sided tape was attached. The release substrate 2 was peeled off from the laminate, and 1.0 μL of pure water was dripped on the surface of the transfer layer (the surface of the antifouling low refractive index layer) using a contact angle meter (DM-300, manufactured by Kyowa Interface Science), and the static contact angle after 10 seconds of dripping was measured according to the θ / 2 method. The measurement was performed 3 times, and the average value was used as the water contact angle of Examples 1-1 to 1-3. The results are shown in Table 1.
[0347] In addition, a laminated body was obtained by laminating the adhesive layer side of the transfer sheet of Comparative Examples 1-1 to 1-3 to the surface of the glass plate to which the double-sided tape was attached. The release substrate was peeled off from the laminated body, and 1.0 μL of pure water was dripped on the surface of the transfer layer (the surface of the antifouling low refractive index layer) using a contact angle meter (DM-300, Kyowa Interface Science), and the static contact angle after dripping for 10 seconds was measured according to the θ / 2 method. The measurement was performed 3 times, and the average value was used as the water contact angle of Comparative Examples 1-1 to 1-3. The results are shown in Table 1.
[0348] 1-2. Antifouling properties (writing and erasability of oily marks (magic))
[0349] A4 white backing paper was placed on a flat workbench, and four sides were fixed with a repair tape (manufactured by 3M, trade name "810-3-18") on the backing paper in a manner that the antifouling low-refractive index layer of the laminate of 10×10 cm produced in the above 1-1 faced upward. Next, on the surface of the antifouling low-refractive index layer, on the bold side of the black oily imprint (trade name "ハイマッキー", manufactured by Zebrah Company, model MO-150-MC), three lines with a width of more than 5 mm and a length of 5 cm were written at 2 cm intervals and then erased, and the writing property and erasability were evaluated according to the following criteria. Furthermore, as a comprehensive evaluation of the writing property and erasability, the antifouling property was evaluated according to the following criteria. The evaluation results of the antifouling property are shown in Table 1.
[0350] <Writing property>
[0351] After 30 seconds from writing, visually observe whether the three lines are bounced. The situation where two or more of the three lines are bounced is evaluated as the situation where the mark is bounced. In addition, the situation where the line shape cannot be maintained and the line is deformed, or the line width or length is shrunk is regarded as the situation where the mark is bounced.
[0352] <Erasability>
[0353] Ten seconds after visual evaluation of writing properties, three lines were wiped with a waste (trade name "Chimwipe", manufactured by Nippon Paper Crecia Co., Ltd., model: S-200), and the number of times the black ink was wiped until no mark was seen after wiping was evaluated.
[0354] <<Antifouling properties>>
[0355] A: The mark bounces off and can be wiped off with one wipe.
[0356] B: The mark does not bounce off, but can be wiped off with 2 to 5 wipes.
[0357] C: The mark does not bounce off and cannot be wiped off even after 5 times.
[0358] 2. Preparation of transfer sheet and molded body
[0359] [Example 1-1]
[0360] The coating liquid 1 for forming an adhesive layer (adhesive layer with heat sealability) of the following formulation is applied to a polyethylene terephthalate film (release substrate 1) with a thickness of 38 μm and a size of 200 mm×600 mm and subjected to release treatment on the surface, and then dried (100°C, 60 seconds) to form an adhesive layer with a thickness of 2 μm.
[0361] Next, a coating liquid 1 for forming a hard coat layer having the following formulation was applied on the adhesive layer and dried (70° C., 30 seconds) to form a coating film, and then irradiated with ultraviolet rays from the hard coat layer side to cure the ionizing radiation curable composition to form a hard coat layer with a thickness of 5 μm.
[0362] Next, the antifouling low refractive index layer-forming coating liquid 1 having the following formulation was applied on the hard coat layer, dried (50° C., 60 seconds) and irradiated with ultraviolet rays to form an antifouling low refractive index layer having a thickness of 100 nm and a refractive index of 1.30.
[0363] Next, a release substrate 2 having a pressure-sensitive adhesive layer on a polyethylene terephthalate film having a thickness of 50 μm (manufactured by San-A.Ken Co., Ltd., trade name "SAT TS1050TRL") was prepared, and the surface of the release substrate 2 on the adhesive layer side was bonded to the antifouling low refractive index layer to obtain the transfer sheet A of Example 1-1. The transfer sheet A of Example 1-1 has a release substrate 1, an adhesive layer, a hard coat layer, an antifouling low refractive index layer, and a release substrate 2 in this order.
[0364] The release substrate 1 of the obtained transfer sheet A was peeled off to obtain the transfer sheet B of Example 1-1. Since the release substrate 1 could be peeled off from the transfer sheet A while leaving the release substrate 2, the transfer sheet A showed a peel strength 2 greater than the peel strength 1.
[0365] Next, the adhesive layer side of the transfer sheet B was overlapped with the adherend (a polycarbonate resin plate (manufactured by Sumitomo Bakelite Co., Ltd., trade name "ECK 100UU", thickness 2 mm)), and heat transfer was performed from the release substrate side of the transfer sheet using a roller thermal printer (manufactured by Daisai Co., Ltd., trade name "RH-300") at a roller temperature of 220 to 240°C and a roller speed of 20 mm / s.
[0366] Next, the release substrate 2 of the transfer sheet B was peeled off to obtain the molded product of Example 1-1. The molded product of Example 1-1 had an adherend, an adhesive layer, a hard coat layer, and an antifouling low-refractive index layer in this order.
[0367] <Adhesive layer forming coating liquid 1>
[0368] ·Acrylic resin 23.0 parts by mass
[0369] (Mitsubishi Chemical Co., Ltd., trade name "Microtech UC026", active ingredient: 40% by mass, methyl ethyl ketone solvent)
[0370] ·Methyl ethyl ketone 74.0 parts by mass
[0371] <Hard coat layer forming coating liquid 1>
[0372] · Photopolymerization initiator 0.5 parts by mass
[0373] (manufactured by BASF, trade name "Omnirad 184")
[0374] · Reactive acrylic polymer 30.0 parts by mass
[0375] (Active ingredient: 35% by mass, methyl ethyl ketone / 2,6-di-tert-butyl-4-methylphenol mixed solvent)
[0376] 5 parts by weight of multifunctional polyurethane acrylate resin
[0377] (manufactured by DIC Corporation, trade name: LUXYDIRERS-543, active ingredient: 80% by mass, toluene solvent)
[0378] Zirconium dioxide 9.0 parts by mass
[0379] (Active ingredient: 70% by mass, methyl ethyl ketone solvent, average particle size 11 nm)
[0380] · Leveling agent 0.2 parts by mass
[0381] (DIC Corporation, trade name "Megafac F-560", active ingredient: 20 mass %)
[0382] · Dilution solvent 55.3 parts by mass
[0383] (Mixed solvent of methyl isobutyl ketone and methyl ethyl ketone in a ratio of 2:8)
[0384] <Antifouling Low Refractive Index Layer Forming Coating Liquid A>
[0385] · Photopolymerization initiator 0.1 parts by mass
[0386] (IGM Resins, trade name "Omnirad 127")
[0387] 1.1 parts by mass of UV curable resin
[0388] (Trifunctional to tetrafunctional alkoxylated pentaerythritol acrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., trade name "NKESTER ATM-4PL")
[0389] ·Hollow silica 6.3 parts by mass (active ingredient: 1.3 parts by mass)
[0390] (average particle size 60nm)
[0391] Solid silicon dioxide 0.9 parts by mass (active ingredient: 0.3 parts by mass)
[0392] (Average particle size 12nm)
[0393] 0.1 parts by mass of fluorine-based antifouling agent (active ingredient: 0.005 parts by mass)
[0394] (DIC Corporation, trade name "Megafac F-568")
[0395] · Dilution solvent 91.5 parts by mass
[0396] (9:1 mixed solvent of methyl isobutyl ketone and propylene glycol monomethyl ether acetate)
[0397] [Example 1-2]
[0398] In the antifouling low-refractive-index layer-forming coating liquid A of Example 1-1, an antifouling low-refractive-index layer-forming coating liquid B was prepared by changing "0.1 parts by mass of a fluorine-based antifouling agent (manufactured by DIC Corporation, trade name "Megafac F-568")" to "a mixture of 0.005 parts by mass of a silicone-based antifouling agent (manufactured by BYK-Chemie Japan Corporation, trade name "BYK-UV3510", active ingredient: 100% by mass) and 0.095 parts by mass of methyl isobutyl ketone", and the coating liquid B was used. Except for this, the transfer sheet A, transfer sheet B and molded body of Example 1-2 were obtained in the same manner as in Example 1-1.
[0399] [Examples 1-3]
[0400] In the antifouling low-refractive-index layer-forming coating liquid A of Example 1-1, 0.05 parts by mass of "0.1 parts by mass of fluorine-based antifouling agent (manufactured by DIC Corporation, trade name "Megafac F-568")" was changed to "a mixture of 0.0025 parts by mass of silicone-based antifouling agent (manufactured by BYK-Chemie Japan, trade name "BYK-UV3510", active ingredient: 100% by mass) and 0.0475 parts by mass of methyl isobutyl ketone" to prepare an antifouling low-refractive-index layer-forming coating liquid C, and the coating liquid C was used. Except for this, the transfer sheet A, transfer sheet B and molded body of Example 1-3 were obtained in the same manner as in Example 1-1.
[0401] [Comparative Example 1-1]
[0402] The antifouling low refractive index layer-forming coating liquid A of the above formulation was applied to a polyethylene terephthalate film (release substrate, size 200 mm×600 mm) with a thickness of 100 μm and a release treatment on the surface, and dried (50° C., 60 seconds) and irradiated with ultraviolet rays to form an antifouling low refractive index layer with a thickness of 100 nm and a refractive index of 1.30.
[0403] Next, the hard coat-forming coating liquid 1 of the above formulation was applied onto the antifouling low refractive index layer and dried (70°C, 30 seconds) to form a coating film, and then, ultraviolet rays were irradiated from the hard coat side to cure the ionizing radiation curable composition to form a hard coat layer with a thickness of 5 μm.
[0404] Next, an anchor layer-forming coating liquid 1 having the following formulation was applied on the hard coat layer, and dried and cured at 100° C. for 1 minute to form an anchor layer having a thickness of 2 μm.
[0405] Next, the coating liquid 1 for forming the adhesive layer (adhesive layer with heat sealability) of the above formulation was applied on the anchor layer, and dried and cured at 100° C. for 1 minute to form an adhesive layer with a thickness of 2 μm, thereby obtaining a transfer sheet of Comparative Example 1-1. The transfer sheet of Comparative Example 1-1 has a release substrate, an antifouling low-refractive index layer, a hard coat layer, an anchor layer, and an adhesive layer in this order.
[0406] Next, the adhesive layer side of the transfer sheet was overlapped with an adherend (a polycarbonate resin plate (manufactured by Sumitomo Bakelite Co., Ltd., trade name "ECK100UU", thickness 2 mm)), and heat transfer was performed from the release substrate side of the transfer sheet using a roller thermal printer (manufactured by Daisai Co., Ltd., trade name "RH-300") at a roller temperature of 220 to 240°C and a roller speed of 20 mm / s.
[0407] Next, the release substrate of the transfer sheet was peeled off to obtain a molded body of Comparative Example 1-1. The molded body of Comparative Example 1-1 had an adherend, an adhesive layer, an anchor layer, a hard coat layer, and an antifouling low-refractive index layer in this order.
[0408] <Anchor layer forming coating liquid 1>
[0409] 7.5 parts by mass of isocyanate resin
[0410] (Active ingredient: 40%, ethyl acetate solvent)
[0411] ·Polyester resin 46.2 parts by mass
[0412] (Active ingredient: 26%, toluene / ethyl acetate / methyl ethyl ketone mixed solvent)
[0413] · Dilution solvent 46.3 parts by mass
[0414] (4:6 mixed solvent of ethyl acetate and toluene)
[0415] [Comparative Example 1-2]
[0416] In the antifouling low-refractive-index layer-forming coating liquid A of Comparative Example 1-1, an antifouling low-refractive-index layer-forming coating liquid B was prepared by changing "0.1 parts by mass of a fluorine-based antifouling agent (manufactured by DIC Corporation, trade name "Megafac F-568")" to "a mixture of 0.005 parts by mass of a silicone-based antifouling agent (manufactured by BYK-Chemie Japan Corporation, trade name "BYK-UV3510", active ingredient: 100% by mass) and 0.095 parts by mass of methyl isobutyl ketone", and the coating liquid B was used. Except for this, the transfer sheet and the molded body of Comparative Example 1-2 were obtained in the same manner as in Comparative Example 1-1.
[0417] [Comparative Examples 1-3]
[0418] In the antifouling low-refractive-index layer-forming coating liquid A of Comparative Example 1-1, 0.05 parts by mass of "0.1 parts by mass of fluorine-based antifouling agent (manufactured by DIC Corporation, trade name "Megafac F-568")" was changed to "a mixture of 0.0025 parts by mass of silicone-based antifouling agent (manufactured by BYK-Chemie Japan, trade name "BYK-UV3510", active ingredient: 100% by mass) and 0.0475 parts by mass of methyl isobutyl ketone" to prepare an antifouling low-refractive-index layer-forming coating liquid C, and the coating liquid C was used. Except for this, the transfer sheet and molded body of Comparative Example 1-3 were obtained in the same manner as in Comparative Example 1-1.
[0419] [Table 1]
[0420]
[0421] From the results in Table 1, it can be confirmed that the molded bodies of Examples 1-1 to 1-3 have high water contact angles and good antifouling properties. In addition, the molded bodies of Examples 1-1 to 1-3 and the molded bodies of Comparative Examples 1-1 to 1-3 have the same formulation of the functional layer, so the results in Table 1 confirm that in the functional layer (antifouling low-refractive index layer) of the molded bodies of Examples 1-1 to 1-3, the antifouling agent as a functional component is biased toward the side opposite to the adherend.
[0422] 3. Comparison of antifouling low refractive index layer's oil and dust resistance, etc.
[0423] 3-1. Preparation of transfer sheet and molded body
[0424] [Example 2-1]
[0425] The antifouling low refractive index layer-forming coating liquid A of Example 1-1 was changed to the antifouling low refractive index layer-forming coating liquid D of the following formulation, and the drying conditions were changed to 60° C. and 1 minute. The transfer sheet A, transfer sheet B and molded body of Example 2-1 were obtained in the same manner as in Example 1-1. In addition, the refractive index of the low refractive index layer of Example 2-1 was 1.33.
[0426] <Antifouling Low-Refractive-Index Layer-Forming Coating Liquid D>
[0427] · Photopolymerization initiator 0.02 parts by mass
[0428] (IGM Resins, trade name "Omnirad 127")
[0429] 0.6 parts by mass of UV curable resin
[0430] (Polyethylene glycol (n≈4) diacrylate, manufactured by Toagosei Co., Ltd., trade name "M-240")
[0431] Hollow silica 6.2 parts by mass (active ingredient: 1.2 parts by mass)
[0432] (Hollow silica with an average particle size of 75 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 20% by mass of the active ingredient)
[0433] Solid silicon dioxide 1.8 parts by mass (active ingredient: 0.7 parts by mass)
[0434] (Solid silica with an average particle size of 12.5 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 40% by mass of the active ingredient)
[0435] ·Silicone leveling agent 0.08 parts by mass
[0436] (Made by Shin-Etsu Chemical Co., Ltd., trade name "KP-420")
[0437] · Dilution solvent 91.3 parts by mass
[0438] (Mixed solvent of methyl isobutyl ketone and 1-methoxy-2-propyl acetate in a ratio of 68:32)
[0439] [Example 2-2]
[0440] Except that “0.6 parts by mass of a UV-curable resin” in the coating liquid D for forming the antifouling low refractive index layer was changed to “0.6 parts by mass of an 80:20 mixture of the following UV-curable resin a and UV-curable resin b”, the transfer sheets A and B and the molded article of Example 2-2 were obtained in the same manner as in Example 2-1. In addition, the refractive index of the low refractive index layer of Example 2-1 was 1.33.
[0441] · UV-curable resin a (polyethylene glycol (n≈4) diacrylate, manufactured by Toagosei Co., Ltd., trade name “M-240”)
[0442] · UV-curable resin b (pentaerythritol (tri / tetra) acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name “KAYARAD PET-30”)
[0443] 3-2. Surface roughness
[0444] Samples were prepared by cutting the molded articles of Examples 2-1 and 2-2 prepared in 3-1 into 5 cm × 5 cm. Using an atomic force microscope (AFM) SPM-9600 manufactured by Shimadzu Corporation, the shape of the molded article of the above sample was measured in the On-Line (measurement) mode in the software: SPM Manager. The following shows the measurement conditions. Then, using the Off-Line (analysis) mode, tilt correction processing was performed to obtain a grayscale image when the height of 0 nm was set to black and the height of 100 nm or more was set to white. In addition, the lowest point within the measurement range was set to “height 0 nm”. The obtained AFM images were analyzed to obtain the Rz (maximum height roughness) and Ra (arithmetic mean roughness) of each sample. The average values of Rz and Rz / Ra of 14 parts were evaluated for each sample. The results are shown in Table 2.
[0445] <AFM measurement conditions>
[0446] Measurement mode: Phase
[0447] Scan range: 5 μm × 5 μm
[0448] Scan speed: 0.8 to 1 Hz
[0449] Number of pixels: 512 × 512
[0450] Cantilever used: NCHR manufactured by Nanosurf (resonance frequency: 320 kHz, spring constant 42 N / m)
[0451] <AFM analysis conditions>
[0452] Tilt correction: Line fitting
[0453] 3-3. Oil and dust resistance test
[0454] The molded bodies of Examples 1-1 to 1-3 and 2-1 to 2-2 were cut into 5 cm×5 cm samples, and a test liquid was prepared by mixing AC dust (ISO12103-1, A2 (Fine)) and olive oil (CAS No. 8001-25-0) at a ratio of 1 / 1 (weight ratio).
[0455] Eight rags (manufactured by AS ONE Co., Ltd., trade name "AZPLEA rag II") were folded and stacked, and firmly attached to the tip of a rod-shaped metal component (the shape of the end surface of the rod was a square of 1 cm x 1 cm) with a rubber band. The side of the rod-shaped metal component to which the rag was attached was immersed in the test liquid, and 5 g of the test liquid was completely contained on the end surface of the rag, thereby obtaining a rod-shaped metal component for wiping.
[0456] The sample is attached to the test bench in such a way that the antifouling low refractive index layer is the upper surface. A counterweight is installed on the rod-shaped metal component for wiping, so that the rag side of the rod-shaped metal component is in contact with the surface of the antifouling low refractive index layer, and the counterweight is reciprocated 10 times at a moving speed of 100 mm / second and a moving distance of 200 mm in one reciprocating stroke (a one-way moving distance of 100 mm). The contact area between the rag and the low refractive index layer is approximately 1 cm, which is roughly equal to the area of the end surface of the rod-shaped metal component. 2 In addition, the test environment was set to a temperature of 23°C ± 1°C and a relative humidity of 50% ± 5% unless otherwise specified.
[0457] Then, the number of damages was evaluated by visual observation from the antifouling low refractive index layer side of the sample under fluorescent light (Panasonic (co., Ltd.) 3-wavelength fluorescent lamp, model: FHF32EX-NH, illumination on the sample was 800 to 1200 Lx, observation distance was 30 cm) and under LED lighting (LED lamp, model: TX-850Re, illumination on the sample was 4000 to 6000 Lx, observation distance was 30 cm). The load was set as the weight of the counterweight, and the maximum load per unit area (g / cm2) was used when no damage (0) was observed after the test. 2 ) represents the oil dust resistance. The test was conducted with n=2, and the average value was taken as the oil dust resistance of each example. The results are shown in Table 2.
[0458] 3-4. Antifouling properties (fingerprint wiping properties)
[0459] The molded bodies of Examples 1-1 to 1-3 and 2-1 to 2-2 were cut into 5 cm × 5 cm samples. The fingertips were pressed on the surface of the antifouling low refractive index layer of the sample to attach fingerprints. Then, the attached fingerprints were wiped with nonwoven fabric (manufactured by Asahi Kasei Corporation, trade name: Ben Cotton), and the number of times until no trace of fingerprints could be seen was evaluated.
[0460] The case where no fingerprints were seen in the 3rd wipe or more was designated as "A", the case where no fingerprints were seen in the 4th to 7th wipe was designated as "B", and the case where fingerprints were seen even after 7th wipe was designated as "C".
[0461] The results are shown in Table 2.
[0462] [Table 2]
[0463]
[0464] Comparing Examples 1-1 to 1-3 with Examples 2-1 to 2-2, Examples 2-1 to 2-2 have good oil dust resistance. The reason for this is believed to be that in the low refractive index layer of Examples 2-1 to 2-2, the hollow silica and the solid silica are arranged in the low refractive index layer. Figure 6 The surface of the low refractive index layer is not roughened. On the other hand, in the low refractive index layers of Examples 1-1 to 1-3, the hollow silica and the solid silica are dispersed uniformly in the low refractive index layer. Figure 7 In that case, the dispersion is not uniform and the surface of the low refractive index layer becomes rough.
[0465] 4. Evaluation and measurement related to peel strength
[0466] The following measurements and evaluations were performed on the transfer sheets obtained in Examples 3-1 to 3-5 and Comparative Example 3-1. The results are shown in Table 3. The atmosphere during each measurement and evaluation was set to a temperature of 23°C ± 5°C and a humidity of 40 to 65%.
[0467] 4-1. Peel strength
[0468] In accordance with the 180 degree peel test of JIS Z0237:2009, the peel strength 1 between the release substrate 1 and the transfer layer and the peel strength 2 between the release substrate 2 and the transfer layer were measured for the release sheets A obtained in Examples 3-1 to 3-5 and Comparative Example 3-1. For Examples 3-1 to 3-5 and Comparative Example 3-1, the peel strengths 1 and 2 were measured three times, and the average values were set as the peel strengths 1 and 2 of Examples 3-1 to 3-5 and Comparative Example 3-1. The sample conditions and measurement conditions were set as follows.
[0469] <Sample Conditions for Measurement of Peel Strength 1>
[0470] A laminated body having a transfer layer formed on a release substrate 1 is prepared (a laminated body having a release substrate 2 laminated on the transfer layer of the laminated body is equivalent to transfer sheet A), and the laminated body is cut into a size of 25 mm in width x 150 mm in length. A substrate with a double-sided tape is prepared as follows: a double-sided tape with a strong adhesive force (751B, manufactured by Teraoka Seisakusho) cut into a length of 150 mm is adhered to a metal ruler (ruler Silver TSU-30N, manufactured by Trasco Nakayama. The same material is used hereinafter). The double-sided tape side of the substrate with the double-sided tape is made to face the transfer layer side of the cut laminated body and the two are fixed at 2 kg / cm 2 The release substrate 1 was peeled off 10 to 20 mm from the end, and the resulting member was used as a sample for measuring the peel strength 1 of Examples 3-1 to 3-5 and Comparative Example 3-1.
[0471] <Sample Condition 1 for Measurement of Peel Strength 2 (Examples 3-1 to 3-5)>
[0472] Place the transfer sheet A on a flat table with the release substrate 2 side facing up for 24 hours (the atmosphere during placement is 23°C ± 5°C and 40-65% humidity). Next, after peeling the release substrate 1 from the transfer sheet A, cut it into a size of 25 mm wide x 150 mm long. Make the double-sided tape side of the substrate with the double-sided tape face the transfer layer side of the cut transfer sheet and press at 2 kg / cm 2 The release substrate 2 was peeled off 10 to 20 mm from the end, and the resulting member was used as a sample for measuring the peel strength 2 of Examples 3-1 to 3-5.
[0473] <Sample Condition 2 for Measurement of Peel Strength 2 (Comparative Example 3-1)>
[0474] Place the transfer sheet A on a flat table with the release substrate 2 side facing up for 24 hours (the atmosphere during placement is 23°C ± 5°C and 40-65% humidity). Next, cut the transfer sheet A into a size of 25 mm in width and 150 mm in length. Make the double-sided tape side of the substrate with the double-sided tape face the release substrate 1 side of the cut transfer sheet A and press at 2 kg / cm 2 The release substrate 2 was peeled off from the end by 10 to 20 mm, and the resulting member was used as a sample for measuring the peel strength 2 of Comparative Example 3-1.
[0475] <Measurement conditions>
[0476] The following configuration is performed: a Tensilon universal testing machine (RTC-1310A, manufactured by Orientec) is used, the adherend (metal ruler) of the prepared measurement sample is fixed to a clamping fixture or the like attached to the Tensilon universal testing machine, the peeled end of the release substrate 1 or 2 is fixed to another clamping fixture, and the release substrate 1 or 2 is stretched in the longitudinal direction. Then, the transfer sheet is stretched 70 mm in the peeling angle 180° direction under the conditions of a peeling speed of 300 mm / min and a room temperature of 23°C, and the load required for peeling is measured. The average load of the moving distance of 10 mm to 30 mm is taken as the peeling force when measuring once, and the average value obtained by performing three measurements is taken as the peeling force.
[0477] 4-2. Releasability of release substrate 1
[0478] Place the transfer sheet A on a flat table with the release substrate 1 side facing up for 24 hours (the atmosphere during placement is 23°C ± 5°C and 40-65% humidity). Next, cut the transfer sheet A into a size of 25 mm in width × 150 mm in length. Make a laminated body in which the double-sided tape side of the substrate with the double-sided tape faces the release substrate 2 side of the cut transfer sheet A and is heated at 2 kg / cm 2 The release properties of the release substrate 1 of the laminate were evaluated according to the following criteria.
[0479] AA: The release substrate 1 can be stably peeled off before the release substrate 2 by a simple operation, and local lifting does not occur at the interface between the release substrate 2 and the transfer layer.
[0480] A: If the operation is performed carefully, the release substrate 1 can be peeled off before the release substrate 2, and local lifting does not occur at the interface between the release substrate 2 and the transfer layer.
[0481] B: If the operation is performed carefully, the release substrate 1 can be peeled off before the release substrate 2 , but local lifting may occur at the interface between the release substrate 2 and the transfer layer.
[0482] C: Even if only the release substrate 1 is carefully peeled off, the release substrate 2 is peeled off first.
[0483] 5. Preparation of release substrate
[0484] The following substrates i to vii were prepared as release substrates 1 and 2 used in Examples 3-1 to 3-5 and Comparative Example 3-1: Substrate i was a plastic film having a release layer, and substrates ii to vii were substrates having a weakly adhesive pressure-sensitive adhesive layer on a plastic film.
[0485] Substrate i: Trade name "FILMBYNA (registered trademark)" manufactured by Fujimori Industries, model: 38E-NSD, substrate thickness: 38 μm
[0486] Substrate ii: SunA.Kaken Co., Ltd., trade name "Suntech MS24", substrate thickness 40 μm
[0487] Substrate iii: SunA.Kaken Co., Ltd., trade name "Suntech Y06F", substrate thickness 60 μm
[0488] Substrate iv: "Suntech Y26F", trade name, manufactured by SunA.Kaken Co., Ltd., substrate thickness: 60 μm
[0489] Substrate v: Trade name "SAT2038T-JSL" manufactured by Sun A. Kaken Co., Ltd., substrate thickness 60 μm
[0490] Substrate vi: Trade name "R304A" manufactured by Toray Film Processing Co., Ltd., substrate thickness 40 μm
[0491] Substrate vii: SunA.Kaken Co., Ltd., trade name "Suntech SAT 1050TRL", substrate thickness 50 μm
[0492] 6. Preparation of transfer film
[0493] [Example 3-1]
[0494] The above-mentioned adhesive layer forming coating liquid 1 is applied on the release substrate 1 (the above-mentioned substrate i) and dried to form an adhesive layer with a thickness of 2 μm. Next, the above-mentioned hard coating layer forming coating liquid 1 is applied on the adhesive layer and dried (70° C., 30 seconds) to form a coating film, and then, ultraviolet rays are irradiated from the hard coating side to cure the ionizing radiation curable composition to form a hard coating layer with a thickness of 5 μm. Next, the release substrate 2 (the above-mentioned substrate ii) is stacked on the hard coating layer to obtain the transfer sheet A of Example 3-1. The transfer sheet A of Example 3-1 has a release substrate 1, an adhesive layer, a hard coating layer and a release substrate 2 in sequence.
[0495] [Examples 3-2 to 3-5], [Comparative Example 3-1]
[0496] Except having changed the release substrate 2 into the substrate described in Table 3, it carried out similarly to Example 3-1, and obtained the transfer sheet A of Examples 3-2 to 3-5 and Comparative Example 3-1.
[0497] [Table 3]
[0498]
[0499] As shown in Table 3, it was confirmed that the transfer sheets A of Examples 3-1 to 3-5, in which the peel strength 2 was greater than the peel strength 1, could peel off the peeling substrate 1 while leaving the peeling substrate 2, thereby obtaining the transfer sheet B. Moreover, the orientation of the functional layer in the thickness direction based on the adherend of the molded body obtained by transferring the transfer layer of the transfer sheet B was the same as the orientation of the functional layer in the thickness direction based on the release substrate 1 of the transfer sheet A. Therefore, the transfer sheets A of Examples 3-1 to 3-5 could fully impart the function of the functional layer with the function biased toward the surface side to the adherend.
[0500] Although not described in the table, the modified examples of Examples 3-1 to 3-5 in which the release substrate 1 was changed to a substrate different from the substrate i were tested. As a result, it was confirmed that if the peel strength 2-peel strength 1 was 100 mN / 25 mm or more, the evaluation of the release property of the release substrate 1 was AA, if the peel strength 2-peel strength 1 was 40 mN / 25 mm or more, the evaluation of the release property of the release substrate 1 was A, and if the peel strength 2-peel strength 1 was 15 mN / 25 mm or more, the evaluation of the release property of the release substrate 1 was B.
[0501] 7. Performance comparison of antifouling low refractive index layer
[0502] 7-1. Preparation of transfer sheet and molded body
[0503] [Example 4-1]
[0504] The above-mentioned adhesive layer forming coating liquid 1 is applied to the release substrate 1 (the above-mentioned substrate i (the product name of Fujimori Industries, Ltd. is "FILMBYNA (registered trademark)", model: 38E-NSD)) and dried to form an adhesive layer with a thickness of 2μm. Next, the above-mentioned hard coating layer forming coating liquid 1 is applied to the adhesive layer and dried (70°C, 30 seconds) to form a coating film, and then, ultraviolet rays are irradiated from the hard coating layer side to cure the ionizing radiation curable composition to form a hard coating layer with a thickness of 5μm. Next, the above-mentioned antifouling low refractive index layer forming coating liquid D is applied to the hard coating layer, dried (50°C, 60 seconds) and irradiated with ultraviolet rays to form an antifouling low refractive index layer with a thickness of 100nm and a refractive index of 1.33. Next, a release substrate 2 (the above-mentioned substrate ii, trade name "SunTech MS24" manufactured by SunA.Kaken Co., Ltd.) was laminated on the antifouling low refractive index layer to obtain the transfer sheet A of Example 4-1. The transfer sheet A of Example 4-1 has a release substrate 1, an adhesive layer, a hard coat layer, an antifouling low refractive index layer and a release substrate 2 in this order.
[0505] Next, the release substrate 1 of the obtained transfer sheet A was peeled off to obtain the transfer sheet B of Example 4-1.
[0506] Next, the adhesive layer side of the transfer sheet B was overlapped with the adherend (a polycarbonate resin plate (manufactured by Sumitomo Bakelite Co., Ltd., trade name "ECK 100UU", thickness 2 mm)), and heat transfer was performed from the release substrate 2 side of the transfer sheet using a roller thermal printer (manufactured by Daisai Co., Ltd., trade name "RH-300") at a roller temperature of 220 to 240°C and a roller speed of 20 mm / s.
[0507] Next, the release substrate 2 of the transfer sheet B was peeled off to obtain a molded product of Example 4-1. The molded product of Example 4-1 had an adherend, an adhesive layer, a hard coat layer, and an antifouling low-refractive index layer in this order.
[0508] [Example 4-2]
[0509] The transfer sheet A, transfer sheet B and molded body of Example 4-2 were obtained in the same manner as in Example 4-1 except that the antifouling low-refractive-index layer-forming coating liquid D was changed to the following antifouling low-refractive-index layer-forming coating liquid E.
[0510] <Antifouling Low-Refractive-Index Layer-Forming Coating Liquid E>
[0511] · Photopolymerization initiator 0.02 parts by mass
[0512] (IGM Resins, trade name "Omnirad 127")
[0513] 0.6 parts by mass of UV curable resin
[0514] (Polyethylene glycol (n≈4) diacrylate, manufactured by Toagosei Co., Ltd., trade name "M-240")
[0515] Hollow silica 6.2 parts by mass (active ingredient: 1.2 parts by mass)
[0516] (Hollow silica with an average particle size of 75 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 20% by mass of the active ingredient)
[0517] Solid silicon dioxide 1.8 parts by mass (active ingredient: 0.7 parts by mass)
[0518] (Solid silica with an average particle size of 12.5 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 40% by mass of the active ingredient)
[0519] · Fluorine leveling agent 0.08 parts by mass
[0520] (Shin-Etsu Chemical Co., Ltd., trade name "X-71-1203M")
[0521] · Dilution solvent 91.3 parts by mass
[0522] (Mixed solvent of methyl isobutyl ketone and 1-methoxy-2-propyl acetate in a ratio of 68:32)
[0523] [Example 4-3]
[0524] The transfer sheet A, transfer sheet B and molded body of Example 4-3 were obtained in the same manner as in Example 4-1 except that the antifouling low-refractive-index layer-forming coating liquid D was changed to the following antifouling low-refractive-index layer-forming coating liquid F.
[0525] <Antifouling Low-Refractive-Index Layer-Forming Coating Liquid F>
[0526] · Photopolymerization initiator 0.02 parts by mass
[0527] (IGM Resins, trade name "Omnirad 127")
[0528] ·Ultraviolet curable resin a 0.3 parts by mass
[0529] (Pentaerythritol (tri / tetra)acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30")
[0530] · Ultraviolet curable resin b 0.3 parts by mass
[0531] (Dipentaerythritol (6 / 5) acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name "KAYARAD DPHA")
[0532] Hollow silica 6.2 parts by mass (active ingredient: 1.2 parts by mass)
[0533] (Hollow silica with an average particle size of 75 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 20% by mass of the active ingredient)
[0534] Solid silicon dioxide 1.8 parts by mass (active ingredient: 0.7 parts by mass)
[0535] (Solid silica with an average particle size of 12.5 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 40% by mass of the active ingredient)
[0536] · Fluorine leveling agent 0.08 parts by mass
[0537] (Shin-Etsu Chemical Co., Ltd., trade name "X-71-1203M")
[0538] · Dilution solvent 91.3 parts by mass
[0539] (Mixed solvent of methyl isobutyl ketone and 1-methoxy-2-propyl acetate in a ratio of 68:32)
[0540] [Example 4-4]
[0541] The transfer sheet A, transfer sheet B and molded body of Example 4-4 were obtained in the same manner as in Example 4-1 except that the antifouling low-refractive-index layer-forming coating liquid D was changed to the following antifouling low-refractive-index layer-forming coating liquid G.
[0542] <Antifouling Low-Refractive-Index Layer-Forming Coating Liquid G>
[0543] · Photopolymerization initiator 0.02 parts by mass
[0544] (IGM Resins, trade name "Omnirad 127")
[0545] ·Ultraviolet curable resin a 0.3 parts by mass
[0546] (Pentaerythritol (tri / tetra)acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30")
[0547] · Ultraviolet curable resin b 0.3 parts by mass
[0548] (Dipentaerythritol (6 / 5) acrylate, manufactured by Nippon Kayaku Co., Ltd., trade name "KAYARAD DPHA")
[0549] Hollow silica 6.2 parts by mass (active ingredient: 1.2 parts by mass)
[0550] (Hollow silica with an average particle size of 75 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 20% by mass of the active ingredient)
[0551] Solid silicon dioxide 1.8 parts by mass (active ingredient: 0.7 parts by mass)
[0552] (Solid silica with an average particle size of 12.5 nm, surface treated with a silane coupling agent having a methacryloyl group. Dispersion containing 40% by mass of the active ingredient)
[0553] ·Silicone leveling agent 0.08 parts by mass
[0554] (Made by Shin-Etsu Chemical Co., Ltd., trade name "KP-420")
[0555] · Dilution solvent 91.3 parts by mass
[0556] (Mixed solvent of methyl isobutyl ketone and 1-methoxy-2-propyl acetate in a ratio of 68:32)
[0557] [Examples 4-5]
[0558] A transfer sheet A, a transfer sheet B, and a molded body of Example 4-5 were obtained in the same manner as in Example 4-1 except that the hard coat layer-forming coating liquid 1 was changed to the following hard coat layer-forming coating liquid 2.
[0559] <Hard coat layer forming coating liquid 2>
[0560] · 23.7 parts by mass of UV curable compound
[0561] (Multifunctional urethane acrylate, manufactured by DIC Corporation, trade name: LUXYDIRERS-543)
[0562] ·Ultraviolet curable compound 18.5 parts by mass
[0563] (Multifunctional urethane acrylate, manufactured by DIC Corporation, trade name: LUXYDIREKS-796)
[0564] ·Ultraviolet absorber 0.74 parts by mass
[0565] (Hydroxyphenyltriazine, manufactured by BASF Japan Co., Ltd., trade name: Tinuvin 477)
[0566] 1.85 parts by mass of UV curable compound
[0567] (Acrylic resin, manufactured by Arakawa Chemical Co., Ltd., trade name DSR-1)
[0568] · Photopolymerization initiator 0.84 parts by mass
[0569] (IGM Resins BV, trade name "Omnirad 184")
[0570] ·Acrylic resin particles 5.17 parts by mass
[0571] (Average particle size 2.0 μm)
[0572] ·Acrylic resin particles 0.72 parts by mass
[0573] (Fumed silica, average particle size 200nm)
[0574] ·Silicone leveling agent 0.27 parts by mass
[0575] (Momentive Performance Materials, trade name: TSF4460)
[0576] · Dilution solvent 48.3 parts by mass
[0577] (Toluene / IPA = 60 / 40 mixed solution)
[0578] [Comparative Example 4-1]
[0579] A transfer sheet A, a transfer sheet B and a molded body of Comparative Example 4-1 were obtained in the same manner as in Example 4-1 except that the release substrate 2 was changed to the substrate vii (trade name “SunTech SAT1050TRL” manufactured by SunA.Kaken Co., Ltd.).
[0580] In the transfer sheet A of Comparative Example 4-1, since the peel strength 2 was smaller than the peel strength 1, in the conventional method, the release substrate 1 could not be peeled off before the release substrate 2. Therefore, in Comparative Example 4-1, a cut was formed on the release substrate 1 side of the transfer sheet A to form a peeling starting point for the release substrate 1, and the release substrate 1 was gradually peeled off while pressing the transfer sheet A from both sides so that the release substrate 2 would not be peeled off, thereby obtaining a transfer sheet B.
[0581] [Comparative Example 4-2]
[0582] The above-mentioned antifouling low refractive index layer forming coating liquid D was applied to the release substrate 1 (the above-mentioned substrate i) and dried (50°C, 60 seconds) and irradiated with ultraviolet rays to form an antifouling low refractive index layer with a thickness of 100nm and a refractive index of 1.33. Next, the above-mentioned hard coating layer forming coating liquid 1 was applied to the antifouling low refractive index layer and dried (70°C, 30 seconds) to form a coating film, and then, ultraviolet rays were irradiated from the hard coating layer side to cure the ionizing radiation curable composition to form a hard coating layer with a thickness of 5μm. Next, the above-mentioned adhesive layer forming coating liquid 1 was applied to the hard coating layer and dried to form an adhesive layer with a thickness of 2μm, thereby obtaining a transfer sheet of Comparative Example 4-2. The transfer sheet of Comparative Example 4-2 has a release substrate 1, an antifouling low refractive index layer, a hard coating layer and an adhesive layer in this order.
[0583] Next, the adhesive layer side of the transfer sheet was overlapped with the adherend (a polycarbonate resin plate (manufactured by Sumitomo Bakelite Co., Ltd., trade name "ECK 100UU", thickness 2 mm)), and heat transfer was performed from the release substrate 1 side of the transfer sheet using a roller thermal printer (manufactured by Daisai Co., Ltd., trade name "RH-300") at a roller temperature of 220 to 240°C and a roller speed of 20 mm / s.
[0584] Next, the release substrate 1 of the transfer sheet was peeled off to obtain a molded body of Comparative Example 4-2. The molded body of Comparative Example 4-2 had an adherend, an adhesive layer, a hard coat layer, and an antifouling low-refractive index layer in this order.
[0585] [Reference Example 4-1]
[0586] The transfer sheet A, transfer sheet B and molded body of Reference Example 4-1 were obtained in the same manner as in Example 4-1 except that the release substrate 2 was changed to the substrate iv (trade name "Suntech Y26F" manufactured by SunA.Kaken Co., Ltd.).
[0587] 7-2. Measurement and evaluation
[0588] The following measurements and evaluations were performed on the molded articles of Examples 4-1 to 4-5, Comparative Examples 4-1 to 4-2, and Reference Example 4-1. The atmosphere during each measurement and evaluation was 23°C ± 5°C and 40 to 65% in humidity unless otherwise specified. In addition, before starting each measurement and evaluation, the molded articles were exposed to the above atmosphere for more than 30 minutes before the measurement and evaluation were performed unless otherwise specified. The results are shown in Table 4.
[0589] (1) XPS analysis
[0590] A measuring sheet was cut out from the molded body of the embodiment. Using an X-ray photoelectron spectrometer, the X-ray photoelectron spectra of the C1s orbital, O1s orbital, Si2p orbital and F1s orbital on the surface of the low refractive index layer of each measuring sheet were measured under the conditions described below. Each X-ray photoelectron spectrum was peak separated to find the ratios of the C element, the O element, the F element and the Si element. In addition, the inorganic component (silicon dioxide) and the organic component (silicone) were peak separated from the X-ray photoelectron spectrum of the Si2p orbital to find the ratio of the Si element belonging to the silica particles (hollow silica particles and non-hollow silica particles) ("inorganic Si" in the table). Each sample was measured at 14 locations and then analyzed with the number of samples n=2. The average value was taken as the element ratio of each embodiment and comparative example. In addition, based on the obtained element ratio, the ratio of the C element (C / Si) when the ratio of the Si element belonging to the silica particles obtained above was converted to 100 atomic % was calculated. In Tables 1 and 2, elements derived from inorganic components other than Si element (inorganic Si element), C element, and F element, such as O element, are referred to as “other elements”, and the total ratio of the elements is indicated.
[0591] <Measurement>
[0592] Installation: AXIS-NOVA by Kratos
[0593] X-ray source: AlKα
[0594] X-ray output: 150W
[0595] Emission current: 10mA
[0596] Accelerating voltage: 15 kV
[0597] Measuring area: 300×700μm
[0598] (2) Surface roughness
[0599] A sample for measurement was prepared by cutting the molded product of the example into a size of 5 cm×5 cm. Using this sample for measurement, Rz (maximum height roughness) and Ra (arithmetic mean roughness) were measured by the same method as in 3-2 above.
[0600] (3) Reflectivity (visual reflectivity Y value)
[0601] A sample (5 cm × 5 cm) was prepared by laminating a black plate (manufactured by KURARAY, trade name: Comoglass DFA2CG 502K (black), thickness 2 mm) to the adherend side of the molded bodies of the examples, comparative examples and reference examples via a 25 μm thick transparent adhesive layer (manufactured by PANAC, trade name: PANACLEAN PD-S1).
[0602] When the direction perpendicular to the surface of the low refractive index layer of the sample is set to 0 degrees, light is incident on the sample from a direction of 5 degrees, and the reflectance (visual reflectance Y value) of the sample is measured based on regular reflection light of the incident light.
[0603] Regarding the reflectivity, the following value representing the visual reflectivity was obtained as the reflectivity, wherein the value was measured using a spectroscopic reflectivity meter (manufactured by Shimadzu Corporation, trade name: UV-2450) under the conditions of a viewing angle of 2 degrees, a C light source, and a wavelength range of 380 to 780 nm, and then calculated using software (device built-in UVPC color measurement Version 3.12) that converts it into the brightness perceived by the human eye.
[0604] The visual reflectance Y value is set to "AA" when it is 0.2% or less, "A" when it is 0.4% or less, "B" when it is more than 0.4% and less than 0.7%, and "B" when it is more than 0.7% and less than 2.0%. - ”.
[0605] (4) Water contact angle
[0606] 1.0 μL of pure water was dripped onto the surface of the molded body (the surface of the antifouling low refractive index layer) of the embodiment, comparative example and reference example, and the static contact angle after 10 seconds of dripping was measured according to the θ / 2 method. The measurement was repeated 3 times, and the average value was set as the water contact angle. The measuring device used was a contact angle meter (product number "DM-300") of Kyowa Interface Science Co., Ltd.
[0607] (5) Antifouling property 1 (Writing and erasability of oily marks)
[0608] A4 white backing paper was placed on a flat workbench, and on the backing paper, the antifouling low refractive index layer of the sample obtained by cutting the molded body into 10×10 cm in the above 7-1 was fixed with repair tape (3M company, trade name "810-3-18") on the four sides. Next, on the surface of the antifouling low refractive index layer, on the bold side of the black oily mark (trade name "ハイマッキー", Zebrah company, model MO-150-MC), three lines with a width of 5 mm or more and a length of 5 cm were written at 2 cm intervals and then erased, and the writing property and erasability were evaluated according to the following criteria. Furthermore, as a comprehensive evaluation of the writing property and erasability, the antifouling property was evaluated according to the following criteria.
[0609] <Writing property>
[0610] After 30 seconds from writing, visually observe whether the three lines are bounced. The situation where two or more of the three lines are bounced is evaluated as the situation where the mark is bounced. In addition, the situation where the line shape cannot be maintained and the line is deformed, or the line width or length is shrunk is regarded as the situation where the mark is bounced.
[0611] <Erasability>
[0612] Ten seconds after visual evaluation of writing properties, three lines were wiped with a waste (trade name "Chimwipe", manufactured by Nippon Paper Crecia Co., Ltd., model: S-200), and the number of times the black ink was wiped until no mark was seen after wiping was evaluated.
[0613] <<Antifouling properties>>
[0614] AA: The mark bounces off and can be wiped off with 1 wipe.
[0615] A: The mark does not bounce off, but can be wiped off with 2 to 3 wipes.
[0616] B: The mark does not bounce off, but can be wiped off with 4 to 5 wipes.
[0617] C: The mark does not bounce off and cannot be wiped off even after 5 times.
[0618] (6) Antifouling property 2 (fingerprint wiping property)
[0619] The molded bodies of the examples, comparative examples and reference examples were cut into 5 cm×5 cm samples. The fingerprint wiping properties were evaluated using the same method and evaluation criteria as in 3-4 above using the measurement samples. The evaluation criteria are shown below.
[0620] A: No fingerprints were visible in the 3rd wipe.
[0621] B: No fingerprints were visible after wiping 4 to 7 times.
[0622] C: Fingerprints can be seen even after wiping 7 times.
[0623] (7) Oil and dust resistance test
[0624] The molded products of Examples, Comparative Examples, and Reference Examples were cut into 5 cm×5 cm samples to prepare the samples for measurement. The oil dust resistance was evaluated by the same method as in 3-3 above.
[0625] (8) Peel strength
[0626] The peel strength 1 of the transfer sheets of Examples, Comparative Examples and Reference Examples was measured by the same method as in 4-1 above.
[0627] In addition, the peel strength 2 of the transfer sheets of Examples 4-1 to 4-5, Comparative Example 4-1, and Reference Example 4-1 was measured by the same method as in 4-1 above. Examples 4-1 to 4-5 and Reference Example 4-1 were prepared by the method of "Sample Condition 1 for Measuring Peel Strength 2" in 4-1 above, and Comparative Example 4-1 was prepared by the method of "Sample Condition 2 for Measuring Peel Strength 2" in 4-1 above.
[0628] (9) Transferability
[0629] The workability when forming a molded body from the transfer sheets of Examples, Comparative Examples, and Reference Examples was evaluated according to the following criteria.
[0630] A: Workability when peeling off the release substrate is good, and workability of transfer is good.
[0631] C1: In normal work, it is difficult to peel the release substrate 1 from the transfer sheet A before the release substrate 2, and the workability of transfer is poor.
[0632] C2: After the transfer sheet B was bonded to an adherend, the peeling force when peeling off the release substrate 2 was too strong, and the workability of transfer was poor.
[0633] [Table 4]
[0634]
[0635] From Table 4, it can be confirmed that the molded bodies of Examples 4-1 to 4-5 can well perform the function of the antifouling low refractive index layer. In particular, it can be confirmed that the molded bodies of Examples 4-1, 4-2, and 4-5, in which the Si element ratio and C / Si of the antifouling low refractive index layer are within the above ranges, have good oil dust resistance. In particular, the molded body of Example 4-1 has excellent oil dust resistance even under LED, which is a more stringent evaluation light source than fluorescent lamps, and the molded body of Example 4-1 has abrasion resistance of the same level as that of an antireflection layer based on a dry process.
[0636] (10-1) Preparation of samples for evaluating glass texture
[0637] The adhesive layer side of the transfer sheet B of Examples 4-1 to 4-4 was overlapped with the adherend (soda glass (1.8 mm thick, 10 cm square) manufactured by Hiraoka Special Glass Manufacturing Co., Ltd.), and heat transfer was performed from the release substrate 2 side of the transfer sheet B using a roller thermal printer (manufactured by Daisai Co., Ltd., trade name "RH-300") at a roller temperature of 220 to 240°C and a roller speed of 20 mm / s.
[0638] Next, the release substrate 2 of the transfer sheet B was peeled off to obtain molded bodies in which the adherends of Examples 4-1 to 4-4 were glass. These molded bodies had an adherend (glass), an adhesive layer, a hard coat layer, and an antifouling low refractive index layer in this order.
[0639] In addition, a molded body in which the adherend of Comparative Example 4-3 is glass was obtained by laminating a commercially available anti-reflection film with optical adhesive (PANAC, trade name: PANACLEAN DSG-17 / PD-C3) on an adherend (soda glass (thickness 1.8 mm, 10 cm square) manufactured by Hiraoka Special Glass Manufacturing Co., Ltd.). The molded body of Comparative Example 4-3 has an adherend (glass), an adhesive layer (thickness 25 μm), a substrate (triacetyl cellulose film with a thickness of 40 μm), a hard coating layer, and an anti-reflection layer in this order. The reflectivity Y value of the molded body of Comparative Example 4-3 was evaluated as A level of less than 0.4%.
[0640] (10-2) Evaluation of glass texture
[0641] The molded article produced in 10-1 was evaluated for touch and sliding properties by "gently sliding the fingertips back and forth five times on the molded article surface" and "gently tapping the molded article surface with a fingernail and confirming the sound". Specifically, the above-mentioned soda glass was used as a standard sample to evaluate whether the touch and sliding properties of the molded article were close to the standard sample.
[0642] Compared with the molded body of Comparative Example 4-3 in which the adherend was glass, the molded bodies of Examples 4-1 to 4-4 in which the adherend was glass had a texture closer to that of glass.
[0643] In the molded bodies of Examples 4-1 to 4-4, where the adherends were glass, the sound produced by the nails was no different from that of the four samples, but in the sliding by the fingertips, Examples 4-2 and 4-3 were better than Examples 4-1 and 4-4. In addition, the reflection Y values of Examples 4-2 and 4-3 were 0.2% or less, which was particularly excellent.
[0644] Description of symbols
[0645] 10: demoulding substrate 1;
[0646] 13: Release substrate;
[0647] 20: release substrate 2;
[0648] 30: transfer layer;
[0649] 31: functional layer 1;
[0650] 32: functional layer 2;
[0651] 100: transfer sheet A;
[0652] 200: transfer sheet B;
[0653] 300: Adhesive;
[0654] 400: laminate C;
[0655] 600: Previous transfer film;
[0656] 800: Molded body.
Claims
1. A method for manufacturing a transfer sheet, wherein: In the method for producing the transfer sheet, the following steps (1) to (2) are performed in sequence: Step (1), coating a transfer layer-forming coating liquid on a release substrate 1 to form a transfer layer comprising at least one functional layer, wherein at least one of the functional layers has a functional bias toward the side opposite to the release substrate 1 in a single layer, and the functional layer having a functional bias toward the side opposite to the release substrate 1 is an antifouling layer or an antifouling low refractive index layer having a functional bias based on an antifouling agent; and Step (2), stacking a release substrate 2 on the transfer layer to obtain a transfer sheet A which sequentially comprises the release substrate 1, the transfer layer and the release substrate 2, wherein the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer, and the difference between the peel strength 2 and the peel strength 1 is greater than 15mN / 25mm and less than 450mN / 25mm.
2. The method for producing a transfer sheet according to claim 1, wherein: In the method for producing the transfer sheet, the following step (3) is further performed: Step (3): The release substrate 1 is peeled off from the transfer sheet A to obtain a transfer sheet B having the transfer layer on the release substrate 2.
3. The method for producing a transfer sheet according to claim 1 or 2, wherein: The peel strength 2 is 100 mN / 25 mm or more and 600 mN / 25 mm or less.
4. A method for producing a molded body, wherein: In the method for producing the molded body, the following steps (4) to (5) are performed in sequence: Step (4), obtaining a laminate C in which the surface of the transfer layer side of the transfer sheet B according to claim 2 is in close contact with an adherend; and In step (5), the release substrate 2 is peeled off from the laminate C to obtain a molded body having a transfer layer on an adherend.
5. The method for producing a molded body according to claim 4, wherein: The peel strength 2 is 100 mN / 25 mm or more and 600 mN / 25 mm or less.
6. A transfer sheet A, wherein: The transfer sheet comprises a release substrate 1, a transfer layer and a release substrate 2 in sequence, the peel strength 2 between the release substrate 2 and the transfer layer is greater than the peel strength 1 between the release substrate 1 and the transfer layer, the difference between the peel strength 2 and the peel strength 1 is greater than 15 mN / 25 mm and less than 450 mN / 25 mm, the transfer layer comprises at least one functional layer, at least one of the functional layers is functionally biased toward the release substrate 2 side within a single layer, and the functional layer functionally biased toward the release substrate 2 side is an antifouling layer or an antifouling low refractive index layer based on the functional bias of an antifouling agent.
7. The transfer sheet A according to claim 6, wherein: The peel strength 2 is 100 mN / 25 mm or more and 600 mN / 25 mm or less.
8. A transfer sheet B, wherein: The transfer sheet is formed by having a transfer layer on a release substrate 2, the transfer layer includes at least one functional layer, at least one of the functional layers is functionally biased toward the release substrate 2 side, and the functional layer functionally biased toward the release substrate 2 side is an antifouling low refractive index layer based on the functional bias of an antifouling agent. The antifouling low-refractive index layer comprises a binder resin and silica particles, the silica particles comprise hollow silica particles and non-hollow silica particles, the ratio of Si element attributable to the silica particles obtained by analyzing the surface area of the antifouling low-refractive index layer on the release substrate 2 side by X-ray photoelectron spectroscopy is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element when the ratio of Si element is converted to 100 atomic % is 180 atomic % or more and 500 atomic % or less, When the thickness of the antifouling low-refractive index layer is divided into three equal parts and defined as a first region, a second region, and a third region in sequence from the side opposite to the release substrate 2, the ratio of the Si element belonging to the silica particles obtained by analyzing any portion within the first region and any portion within the second region by X-ray photoelectron spectroscopy is greater than 10.0 atomic % and less than 18.0 atomic %, and the ratio of the C element when the ratio of the Si element is converted to 100 atomic % is greater than 180 atomic % and less than 500 atomic %.
9. A molded body, wherein The molded body is formed by having a transfer layer on an adherend, the transfer layer having at least one functional layer, at least one of the functional layers having a function biased toward the side opposite to the adherend, and the functional layer having a function biased toward the side opposite to the adherend is an antifouling low-refractive index layer having a function biased toward the side opposite to the adherend based on an antifouling agent. The antifouling low-refractive index layer comprises a binder resin and silica particles, the silica particles comprising hollow silica particles and non-hollow silica particles, the ratio of Si element attributable to the silica particles obtained by analyzing a surface region of the antifouling low-refractive index layer on a side opposite to the adherend by X-ray photoelectron spectroscopy is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element when the ratio of Si element is converted to 100 atomic % is 180 atomic % or more and 500 atomic % or less, When the thickness of the antifouling low-refractive index layer is divided into three equal parts and defined as a first region, a second region, and a third region in sequence from the adherend side, the ratio of the Si element belonging to the silica particles obtained by analyzing any portion within the first region and any portion within the second region by X-ray photoelectron spectroscopy is greater than 10.0 atomic % and less than 18.0 atomic %, and the ratio of the C element when the ratio of the Si element is converted to 100 atomic % is greater than 180 atomic % and less than 500 atomic %.
10. The molded article according to claim 9, wherein The adherend is one selected from glass, ceramics and resin or a mixture thereof.
11. The molded article according to claim 9, wherein The adherend is glass, and the layer closest to the adherend among the layers constituting the transfer layer contains a resin having one or more functional groups selected from a carboxyl group and a methoxy group.
12. A front panel for an image display device, wherein: The front panel for an image display device is composed of the molded article according to any one of claims 9 to 11.
13. An image display device having a front panel on a display element, wherein: The front panel is the molded product according to any one of claims 9 to 11.
Citation Information
Patent Citations
Antireflection film for transferring, and transferred material and display apparatus using the same
JP2008151930A
Transfer antireflection film
JP2009056674A
Antidazzle sheet for transfer
JP2009072954A
Transfer medium, polarizing plate, and image display device
JP2014130298A
Transfer material, substrate with transfer layer, touch panel, manufacturing methods therefor, and information display device
CN105142925A